Magnetic recording medium, magnetic recording / reproducing device, and magnetic recording medium cartridge

JP7639880B2Active Publication Date: 2025-03-05SONY GROUP CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023194595
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-11-15
Publication Date
2025-03-05
Estimated Expiration
2039-08-16

AI Technical Summary

Benefits of technology

【0008】 本開示の一実施形態としての磁気記録媒体および磁気記録再生装置では、下地層が比較的薄いので、材料コストが低減されるうえ、1カートリッジあたりの巻量向上が期待される。また、磁気記録媒体の全体のBET比表面積は、3.5m2/g以上であるので、下地層を薄くした場合であっても、潤滑剤が磁気記録媒体の表面に安定して供給される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639880000005
    Figure 0007639880000005
  • Figure 0007639880000006
    Figure 0007639880000006
  • Figure 0007639880000007
    Figure 0007639880000007
Patent Text Reader

Abstract

To provide a magnetic recording medium capable of exerting a favorable travelling performance when in use.SOLUTION: This magnetic recording medium is a tape-shaped magnetic recording medium, and comprises a substrate, an underlayer provided on the substrate, and a magnetic layer provided on the underlayer. The substrate includes polyester as a main component. The average thickness of the underlayer is 0.9 μm or less. The underlayer and the magnetic layer include lubricants. The magnetic layer has a surface with multiple pore portions and an arithmetic average roughness Ra of the surface is 2.5 nm or less. BET specific surface area of the entire magnetic recording medium in a state where the lubricant is removed therefrom and dried, is 3.5 m2 / g or more. The squareness ratio in the vertical direction is 65% or more. The average thickness of the magnetic layer is 90 nm or less. The average thickness of the magnetic recording medium is 5.6 μm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a magnetic recording medium, as well as a magnetic recording / reproducing device and a magnetic recording medium cartridge using the same. [Background technology]

[0002] Tape-type magnetic recording media are widely used to store electronic data. For example, Patent Document 1 describes smoothing the surface of the magnetic layer in order to improve the electromagnetic conversion characteristics of the magnetic recording media. The same document also describes adding a lubricant to the magnetic layer in order to reduce friction caused by contact between the magnetic recording media and the head. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2006-65953 A Summary of the Invention [Problem to be solved by the invention]

[0004] Incidentally, in such tape-like magnetic recording media, there is a demand for stable recording and reproduction of information during recording and reproduction.

[0005] Therefore, there is a demand for a magnetic recording medium that can exhibit good running performance during use. [Means for solving the problem]

[0006] A magnetic recording medium according to an embodiment of the present disclosure is a tape-shaped magnetic recording medium, and includes a substrate, an underlayer provided on the substrate, and a magnetic layer provided on the underlayer. The substrate contains polyester as a main component. The underlayer has an average thickness of 0.9 μm or less. The underlayer and the magnetic layer contain a lubricant. The magnetic layer has a surface provided with a large number of holes, and the arithmetic mean roughness Ra of the surface is 2.5 nm or less. The overall BET specific surface area of ​​the magnetic recording medium after the lubricant has been removed and the magnetic recording medium is in a dried state is 3.5 m. 2 / g or more. The squareness ratio in the perpendicular direction of the magnetic recording medium is 65% or more. The average thickness of the magnetic layer is 90 nm or less. The average thickness of the magnetic recording medium is 5.6 μm or less.

[0007] A magnetic recording and reproducing device according to one embodiment of the present disclosure includes a feed device capable of sequentially feeding out the magnetic recording medium (by rotating a wound body of the magnetic recording medium), a winding device capable of winding up the magnetic recording medium fed out from the feed device, and a magnetic head capable of writing information to the magnetic recording medium and reading information from the magnetic recording medium while coming into contact with the magnetic recording medium traveling from the feed device to the winding device.

[0008] In the magnetic recording medium and the magnetic recording and reproducing device according to the embodiment of the present disclosure, the underlayer is relatively thin, so that the material cost is reduced and the number of windings per cartridge is expected to be improved. In addition, the BET specific surface area of ​​the entire magnetic recording medium is 3.5 m 2 / g or more, the lubricant is stably supplied to the surface of the magnetic recording medium even if the underlayer is made thin. [Brief description of the drawings]

[0009] [Figure 1] 1 is a cross-sectional view of a magnetic recording medium according to an embodiment of the present disclosure. [Figure 2A] 2 is a schematic explanatory diagram showing the layout of a data band and a servo band in the magnetic recording medium shown in FIG. [Figure 2B]FIG. 2B is a schematic explanatory diagram showing an enlarged view of the data band shown in FIG. 2A. [Diagram 3] FIG. 2 is a cross-sectional view that typically illustrates the cross-sectional structure of an ε iron oxide particle contained in the magnetic layer shown in FIG. [Figure 4] 2 is a schematic diagram of a recording / reproducing device that uses the magnetic recording medium shown in FIG. [Diagram 5] FIG. 11 is a cross-sectional view that typically illustrates a cross-sectional structure of an ε-iron oxide particle as a modified example. [Figure 6] FIG. 11 is a cross-sectional view of a magnetic recording medium as another modified example. [Figure 7] FIG. 2 is a schematic diagram showing a tensile tester. [Figure 8] FIG. 2 is a schematic diagram illustrating a method for measuring a dynamic friction coefficient. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the drawings. The description will be made in the following order. 1. One embodiment 1-1. Structure of magnetic recording media 1-2. Manufacturing method of magnetic recording media 1-3. Configuration of recording / playback device 1-4.Effects 2. Variations

[0011] <1. One embodiment> [1-1 Configuration of magnetic recording medium 10] FIG. 1 shows an example of a cross-sectional configuration of a magnetic recording medium 10 according to an embodiment of the present disclosure. As shown in FIG. 1, the magnetic recording medium 10 has a laminated structure in which multiple layers are laminated. Specifically, the magnetic recording medium 10 includes a long tape-shaped substrate 11, an underlayer 12 provided on one main surface 11A of the substrate 11, a magnetic layer 13 provided on the underlayer 12, and a back layer 14 provided on the other main surface 11B of the substrate 11. A surface 13S of the magnetic layer 13 is the surface against which the magnetic head runs while contacting it. The underlayer 12 and the back layer 14 are provided as necessary, and may not be required. The average thickness of the magnetic recording medium 10 may be, for example, 5.6 μm or less. The Young's modulus of the magnetic recording medium 10 may be, for example, 7.78 GPa or less.

[0012] The Young's modulus of the magnetic recording medium 10 is measured, for example, by a tensile tester. As shown in FIG. 7, the tensile tester includes a main body 81, a movable part 82 that can move up and down in the vertical direction relative to the main body 81, a gripping jig 83 attached to the main body 81, and a gripping jig 84 attached to the movable part 82. The gripping jig 83 and the gripping jig 84 are jigs for gripping the ends of the measurement sample 10S cut out from the magnetic recording medium 10. As the tensile tester, for example, the "AG-100D" manufactured by Shimadzu Corporation can be used.

[0013] When the Young's modulus in the longitudinal direction of the magnetic recording medium 10 is to be measured using the tensile tester shown in FIG. 7, the magnetic recording medium 10 is first cut to a length of 180 mm to prepare a measurement sample 10S. Next, a gripping jig 83 and a gripping jig 84 capable of fixing the measurement sample 10S over the entire width (for example, 1 / 2 inch) are attached to a main body 81 and a movable part 82 of the tensile tester, respectively, and then the two ends in the longitudinal direction of the measurement sample 10S are fixed by the gripping jig 83 and the gripping jig 84, respectively. At this time, the distance between the gripping jig 83 and the gripping jig 84 is set to 100 mm. Then, the distance between the gripping jig 83 and the gripping jig 84 is widened in the longitudinal direction of the measurement sample 10S at a pulling speed of 0.1 mm / min, and stress is applied to the measurement sample 10S. Based on the change in stress and the amount of elongation at this time, the Young's modulus can be calculated using the following formula. E = {(ΔN / S) / (ΔX / L)} × 10 6 [N / m 2 ] however, ΔN: Change in stress [N] S: Cross-sectional area of ​​measurement sample 10S [mm 2 ] ΔX: Elongation amount [mm] L: Distance between gripping jigs [mm] The stress range is set to 0.5N to 1.0N, and the change in stress (ΔN) and the amount of elongation (ΔX) at this range are used for calculation.

[0014] The magnetic recording medium 10 is in the form of a long tape, and runs along its own longitudinal direction during recording and reproducing operations. The magnetic recording medium 10 is preferably used in a recording and reproducing device equipped with a ring-type head as a recording head, for example.

[0015] (Base 11) The substrate 11 is a non-magnetic support that supports the underlayer 12 and the magnetic layer 13. The substrate 11 is in the form of a long film. The upper limit of the average thickness of the substrate 11 is preferably 4.2 μm or less, more preferably 4.0 μm or less. When the upper limit of the average thickness of the substrate 11 is 4.2 μm or less, the recording capacity that can be recorded in one data cartridge can be made higher than that of a typical magnetic recording medium. The lower limit of the average thickness of the substrate 11 is preferably 3 μm or more, more preferably 3.2 μm or more. When the lower limit of the average thickness of the substrate 11 is 3 μm or more, a decrease in the strength of the substrate 11 can be suppressed.

[0016] The average thickness of the substrate 11 is obtained as follows. First, a magnetic recording medium 10 with a width of 1 / 2 inch is prepared and cut into a length of 250 mm to prepare a sample. Next, layers other than the substrate 11 of the sample, i.e., the underlayer 12, the magnetic layer 13, and the back layer 14, are removed with a solvent such as MEK (methyl ethyl ketone) or dilute hydrochloric acid. Next, the thickness of the sample substrate 11 is measured at five or more positions using a Mitsutoyo Laser Hologram (LGH-110C) as a measuring device, and the measured values ​​are simply averaged (arithmetic average) to calculate the average thickness of the substrate 11. Note that the measurement positions are selected randomly from the sample.

[0017] The base 11 contains, for example, polyesters as a main component. In addition to polyesters, the base 11 may contain at least one of polyolefins, cellulose derivatives, vinyl resins, and other polymer resins. When the base 11 contains two or more of the above materials, the two or more materials may be mixed, copolymerized, or laminated.

[0018] The polyesters contained in the base 11 include, for example, at least one of PET (polyethylene terephthalate), PEN (polyethylene naphthalate), PBT (polybutylene terephthalate), PBN (polybutylene naphthalate), PCT (polycyclohexylene dimethylene terephthalate), PEB (polyethylene-p-oxybenzoate), and polyethylene bisphenoxycarboxylate.

[0019] The polyolefins contained in the base 11 include, for example, at least one of PE (polyethylene) and PP (polypropylene). The cellulose derivatives include, for example, at least one of cellulose diacetate, cellulose triacetate, CAB (cellulose acetate butyrate) and CAP (cellulose acetate propionate). The vinyl resins include, for example, at least one of PVC (polyvinyl chloride) and PVDC (polyvinylidene chloride).

[0020] Other polymer resins contained in the base 11 include, for example, at least one of PA (polyamide, nylon), aromatic PA (aromatic polyamide, aramid), PI (polyimide), aromatic PI (aromatic polyimide), PAI (polyamideimide), aromatic PAI (aromatic polyamideimide), PBO (polybenzoxazole, such as Zylon (registered trademark)), polyether, PEK (polyetherketone), polyetherester, PES (polyethersulfone), PEI (polyetherimide), PSF (polysulfone), PPS (polyphenylene sulfide), PC (polycarbonate), PAR (polyarylate), and PU (polyurethane).

[0021] (Magnetic layer 13) The magnetic layer 13 is a recording layer for recording signals. The magnetic layer 13 contains, for example, a magnetic powder, a binder, and a lubricant. The magnetic layer 13 may further contain additives such as conductive particles, an abrasive, and an anti-rust agent, as necessary.

[0022] The magnetic layer 13 has a surface 13S on which a large number of holes 13A are provided. A lubricant is stored in the large number of holes 13A. It is preferable that the large number of holes 13A extend in a direction perpendicular to the surface of the magnetic layer 13. This is because this can improve the supply of the lubricant to the surface 13S of the magnetic layer 13. Note that some of the large number of holes 13A may extend in the vertical direction.

[0023] The arithmetic mean roughness Ra of the surface 13S of the magnetic layer 13 is 2.5 nm or less, preferably 2.2 nm or less, more preferably 1.9 nm or less. When the arithmetic mean roughness Ra is 2.5 nm or less, excellent electromagnetic conversion characteristics can be obtained. The lower limit of the arithmetic mean roughness Ra of the surface 13S of the magnetic layer 13 is preferably 0.8 nm or more, more preferably 1.0 nm or more. When the lower limit of the arithmetic mean roughness Ra of the surface 13S of the magnetic layer 13 is 0.8 nm or more, deterioration of running properties due to increased friction can be suppressed.

[0024] The arithmetic mean roughness Ra of the surface 13S is found as follows. First, the surface of the magnetic layer 13 is observed with an AFM (Atomic Force Microscope) to obtain an AFM image of 40 μm×40 μm. A Nano Scope IIIa D3100 manufactured by Digital Instruments is used as the AFM, a single crystal silicon cantilever is used, and measurements are performed with a tapping frequency of 200 Hz to 400 Hz tuning. For example, an "SPM Probe NCH Normal Type PointProbe L (cantilever length)=125 um" manufactured by Nano World cantilever can be used. Next, the AFM image is divided into 512 x 512 (= 262,144) measurement points, and the height Z(i) (i: measurement point number, i = 1 to 262,144) is measured at each measurement point. The heights Z(i) of each measurement point are simply averaged (arithmetic mean) to obtain the average height (average surface) Zave (= (Z(1) + Z(2) + ··· + Z(262,144)) / 262,144). Next, the deviation Z"(i) (= |Z(i)-Zave|) from the average center line at each measurement point is obtained, and the arithmetic mean roughness Ra [nm] (= (Z"(1) + Z"(2) + ··· + Z"(262,144)) / 262,144) is calculated. In this case, the data used is filtered using Flatten order 2 and planefit order 3 XY as image processing.

[0025] The lower limit of the overall BET specific surface area of ​​the magnetic recording medium 10 in a dry state after removing the lubricant is 3.5 m 2 / g or more, preferably 4.0m 2 / g or more, more preferably 4.5m 2 / g or more, and even more preferably 5.0m 2 / g or more. The lower limit of the BET specific surface area is 3.5 m 2 / g or more, it is possible to suppress a decrease in the amount of lubricant supplied between the surface of the magnetic layer 13 and the magnetic head even after repeated recording or reproduction (i.e., even after the magnetic head is in contact with the surface of the magnetic recording medium 10 and is repeatedly run), and therefore it is possible to suppress an increase in the dynamic friction coefficient.

[0026] The upper limit of the overall BET specific surface area of ​​the magnetic recording medium 10 in a dry state after removal of the lubricant is preferably 7.0 m 2 / g or less, more preferably 6.0m 2 / g or less, and even more preferably 5.5m 2 / g or less. The upper limit of the BET specific surface area is 7.0 m 2 If the lubricant content is less than 1 / g, the lubricant can be sufficiently supplied without being depleted even after multiple runs, and therefore an increase in the dynamic friction coefficient can be suppressed.

[0027] The magnetic recording medium 10 in this state in which the lubricant has been removed and the magnetic recording medium 10 has been dried refers to the magnetic recording medium 10 that has been immersed in hexane at room temperature for 24 hours, then removed from the hexane and allowed to dry naturally.

[0028] The average pore diameter of the entire magnetic recording medium 10 as determined by the BJH method is 6 nm to 12 nm, preferably 7 nm to 10 nm, and more preferably 7.5 nm to 10 nm. When the average pore diameter is 6 nm to 12 nm, the effect of suppressing the increase in the dynamic friction coefficient described above can be further improved.

[0029] The BET specific surface area and pore distribution (pore volume, pore diameter of maximum pore volume during desorption) are calculated as follows. 2 A magnetic recording medium 10 with a size approximately 10% larger than the tape is immersed in hexane (an amount sufficient to fully immerse the tape, for example, 150 mL) for 24 hours, and then naturally dried to obtain a size of 0.1265 m2. 2 (For example, cut off 50 cm from both ends of the dried tape to prepare a measurement sample x 10 m.) Next, a specific surface area / pore distribution measurement device is used to determine the pore distribution (pore volume and average pore diameter) according to the BJH method. The measurement device and measurement conditions are shown below. In this way, the average pore diameter is measured. Measurement environment: Room temperature Measurement equipment: Micromeritics 3FLEX Measurement adsorbate: N2 gas Measurement pressure range (P / P0): 0~0.995 For the measurement pressure range, the pressure is changed as shown in the following table. The pressure values ​​in the following table are relative pressures P / P0. In the following table, for example, in step 1, the pressure is changed from a starting pressure of 0.000 to a final pressure of 0.010, changing by 0.001 per 10 seconds. When the pressure reaches the final pressure, the pressure change in the next step is performed. The same applies to steps 2 to 10. However, in each step, if the pressure has not reached equilibrium, the device waits for the pressure to reach equilibrium before moving on to the next step. [Table 1]

[0030] The magnetic layer 13 preferably has a plurality of servo bands SB and a plurality of data bands DB in advance, as shown in FIG. 2A, for example. FIG. 2A is a schematic explanatory diagram showing the layout of the data bands DB and the servo bands SB in the magnetic recording medium 10, and shows the layout in a plane perpendicular to the lamination direction in the magnetic recording medium 10 having a laminated structure. As shown in FIG. 2A, the plurality of servo bands SB are provided at equal intervals in the width direction of the magnetic recording medium 10. The width direction of the magnetic recording medium 10 is a direction perpendicular to both the longitudinal direction of the magnetic recording medium 10 and the lamination direction of the magnetic recording medium 10. A data band DB is provided between the servo bands SB adjacent to each other in the width direction. A servo signal for tracking control of the magnetic head is written in advance in the servo bands SB. User data is recorded in the data bands DB.

[0031] The total area S of the servo bands SB relative to the area S of the surface 13S of the magnetic layer 13 SB The ratio of R S (=(S SBFrom the viewpoint of ensuring a high recording capacity, the upper limit of the ratio of the total area S of the servo bands SB to the surface area S of the magnetic layer 13 is preferably 4.0% or less, more preferably 3.0% or less, and even more preferably 2.0% or less. SB The ratio of R S The lower limit is preferably 0.8% or more, from the viewpoint of ensuring five or more servo tracks.

[0032] The total area S of the servo bands SB relative to the surface area S of the magnetic layer 13 SB The ratio of R S For example, the servo bandwidth W can be measured by developing the magnetic recording medium 10 using a ferricolloid developer (Sigma Car Q, manufactured by Sigma High Chemical Co., Ltd.) and then observing the developed magnetic recording medium 10 with an optical microscope. SB and the number of servo bands SB. Next, calculate the ratio R from the following formula: S Request. Ratio R S [%]=(((Servo bandwidth W SB )×(number of servo bands) / (width of magnetic recording medium 10)×100

[0033] The number of servo bands SB is preferably 5 or more, and more preferably 5+4n or more (where n is a positive integer). If the number of servo bands SB is 5 or more, the effect on the servo signal due to dimensional changes in the width direction of the magnetic recording medium 10 can be suppressed, and stable recording and reproducing characteristics with little off-track can be ensured.

[0034] Servo Bandwidth W SB From the viewpoint of ensuring a high recording capacity, the upper limit of the servo band width W is preferably 95 μm or less, more preferably 60 μm or less, and even more preferably 30 μm or less. SB From the viewpoint of recording head manufacturing, the lower limit of the servo band width W is preferably 10 μm or more. SBThe width of the servo band width W is obtained as follows. First, the magnetic recording medium 10 is developed using a ferricolloid developer (Sigma Car Q, manufactured by Sigma High Chemical Co., Ltd.). Next, the developed magnetic recording medium 10 is observed with an optical microscope to determine the servo band width W SB The width can be measured.

[0035] As shown in FIG. 2B, the magnetic layer 13 is configured so that a plurality of data tracks Tk can be formed on the data band DB. In this case, the data track width W Tk From the viewpoint of ensuring a high recording capacity, the upper limit of the data track width W is preferably 2.0 μm or less, more preferably 1.5 μm or less, and even more preferably 1.0 μm or less. Tk From the viewpoint of the magnetic particle size, the lower limit is preferably 0.02 μm or more.

[0036] From the viewpoint of ensuring a high recording capacity, the magnetic layer 13 is configured to be capable of recording data such that the minimum value of the distance L between magnetization reversals is preferably 48 nm or less, more preferably 44 nm or less, and even more preferably 40 nm or less. The lower limit of the minimum value of the distance L between magnetization reversals is taken into consideration from the viewpoint of the magnetic grain size.

[0037] The upper limit of the average thickness of the magnetic layer 13 is preferably 90 nm or less, particularly preferably 80 nm or less, more preferably 70 nm or less, and even more preferably 50 nm or less. If the upper limit of the average thickness of the magnetic layer 13 is 90 nm or less, when a ring-type head is used as the recording head, self-demagnetization loss and thickness loss can be reduced, thereby improving the electromagnetic conversion characteristics.

[0038] The lower limit of the average thickness of the magnetic layer 13 is preferably 35 nm or more. If the upper limit of the average thickness of the magnetic layer 13 is 35 nm or more, output can be ensured when an MR head is used as the reproducing head, and therefore the electromagnetic conversion characteristics can be improved.

[0039] The average thickness of the magnetic layer 13 is determined as follows. First, a carbon film is formed by vapor deposition on the surface 13S of the magnetic layer 13 and the surface 14S of the back layer 14 of the magnetic recording medium 10, and then a tungsten thin film is further formed by vapor deposition on the carbon film covering the surface 13S of the magnetic layer 13. These carbon and tungsten films protect the sample during the thinning process described below.

[0040] Next, the magnetic recording medium 10 is processed by a FIB (Focused Ion Beam) method or the like to be sliced. When the FIB method is used, a carbon film and a tungsten thin film are formed as protective films as a pretreatment for observing a TEM image of the cross section described later. The carbon film is formed on the magnetic layer side surface and the back layer side surface of the magnetic recording medium 10 by a vapor deposition method, and the tungsten thin film is further formed on the magnetic layer side surface by a vapor deposition method or a sputtering method. The slice is performed along the length direction (longitudinal direction) of the magnetic recording medium 10. That is, the slice forms a cross section parallel to both the longitudinal direction and the thickness direction of the magnetic recording medium 10. The cross section of the obtained sliced ​​sample is observed under the following conditions by a transmission electron microscope (TEM) to obtain a TEM image. The magnification and acceleration voltage may be appropriately adjusted depending on the type of device. Equipment: TEM (Hitachi H9000NAR) Acceleration voltage: 300 kV Magnification: 100,000x

[0041] Next, using the obtained TEM image, the thickness of the magnetic layer 13 is measured at at least 10 positions in the longitudinal direction of the magnetic recording medium 10. The obtained measured values ​​are simply averaged (arithmetic average) to obtain the average thickness of the magnetic layer 13. The measurement positions are selected randomly from the test piece.

[0042] (magnetic powder) The magnetic powder includes, for example, a powder of nanoparticles containing ε-iron oxide (hereinafter referred to as "ε-iron oxide particles"). Even fine particles of ε-iron oxide particles can obtain high coercivity. It is preferable that the ε-iron oxide contained in the ε-iron oxide particles has a crystal orientation preferentially in the thickness direction (perpendicular direction) of the magnetic recording medium 10.

[0043] 3 is a cross-sectional view showing a schematic example of the cross-sectional structure of the ε iron oxide particles 20 contained in the magnetic layer 13. As shown in FIG. 3, the ε iron oxide particles 20 are spherical or nearly spherical, or cubic or nearly cubic. Since the ε iron oxide particles 20 have the above-mentioned shapes, when the ε iron oxide particles 20 are used as the magnetic particles, the contact area between the particles in the thickness direction of the magnetic recording medium 10 can be reduced and the aggregation between the particles can be suppressed, compared to when hexagonal plate-shaped barium ferrite particles are used as the magnetic particles. This improves the dispersibility of the magnetic powder, and makes it possible to obtain a better SNR (Signal-to-Noise Ratio).

[0044] The ε-iron oxide particle 20 may have, for example, a core-shell structure. Specifically, as shown in Fig. 3, the ε-iron oxide particle 20 includes a core portion 21 and a two-layered shell portion 22 provided around the core portion 21. The two-layered shell portion 22 includes a first shell portion 22a provided on the core portion 21 and a second shell portion 22b provided on the first shell portion 22a.

[0045] The core portion 21 of the ε-iron oxide particle 20 contains ε-iron oxide. The ε-iron oxide contained in the core portion 21 preferably has ε-Fe2O3 crystals as a main phase, and more preferably is made of single-phase ε-Fe2O3.

[0046] The first shell portion 22a covers at least a part of the periphery of the core portion 21. Specifically, the first shell portion 22a may cover a part of the periphery of the core portion 21, or may cover the entire periphery of the core portion 21. From the viewpoint of ensuring sufficient exchange coupling between the core portion 21 and the first shell portion 22a and improving magnetic characteristics, it is preferable that the entire surface of the core portion 21 is covered.

[0047] The first shell portion 22a is a so-called soft magnetic layer, and includes a soft magnetic material such as α-Fe, a Ni-Fe alloy, an Fe-Si-Al alloy, etc. The α-Fe may be obtained by reducing ε-iron oxide included in the core portion 21.

[0048] The second shell portion 22b is an oxide coating serving as an anti-oxidation layer. The second shell portion 22b includes α-iron oxide, aluminum oxide, or silicon oxide. The α-iron oxide includes at least one type of iron oxide, for example, Fe3O4, Fe2O3, and FeO. When the first shell portion 22a includes α-Fe (soft magnetic material), the α-iron oxide may be obtained by oxidizing the α-Fe included in the first shell portion 22a.

[0049] By having the first shell portion 22a as described above, the coercive force Hc of the core portion 21 alone can be kept large to ensure thermal stability, while the coercive force Hc of the entire ε-iron oxide particle (core-shell particle) 20 can be adjusted to a coercive force Hc suitable for recording. Furthermore, by having the second shell portion 22b as described above, the ε-iron oxide particle 20 can be prevented from deteriorating in the properties of the ε-iron oxide particle 20 due to rust or the like occurring on the particle surface caused by exposure of the ε-iron oxide particle 20 to air during and before the manufacturing process of the magnetic recording medium 10. Therefore, by covering the first shell portion 22a with the second shell portion 22b, deterioration in the properties of the magnetic recording medium 10 can be prevented.

[0050] The average particle size (average maximum particle size) of the magnetic powder is preferably 25 nm or less, more preferably 8 nm to 22 nm, and even more preferably 12 nm to 22 nm. In the magnetic recording medium 10, the area with a size of 1 / 2 of the recording wavelength becomes the actual magnetization area. Therefore, by setting the average particle size of the magnetic powder to half the shortest recording wavelength or less, a good S / N ratio can be obtained. Therefore, when the average particle size of the magnetic powder is 22 nm or less, good electromagnetic conversion characteristics (e.g., SNR) can be obtained in a high recording density magnetic recording medium 10 (e.g., a magnetic recording medium 10 configured to be able to record signals at the shortest recording wavelength of 50 nm or less). On the other hand, when the average particle size of the magnetic powder is 8 nm or more, the dispersibility of the magnetic powder is further improved, and better electromagnetic conversion characteristics (e.g., SNR) can be obtained.

[0051] The average aspect ratio of the magnetic powder is preferably 1 or more and 3.0 or less, more preferably 1 or more and 2.8 or less, and even more preferably 1 or more and 1.8 or less. When the average aspect ratio of the magnetic powder is within the range of 1 or more and 3.0 or less, aggregation of the magnetic powder can be suppressed, and the resistance applied to the magnetic powder when the magnetic powder is vertically oriented in the process of forming the magnetic layer 13 can be suppressed. Therefore, the vertical orientation of the magnetic powder can be improved.

[0052] The average particle size and average aspect ratio of the magnetic powder are obtained as follows. First, the magnetic recording medium 10 to be measured is processed and thinned by FIB (Focused Ion Beam) method or the like. The thinning is performed along the length direction (longitudinal direction) of the magnetic tape. That is, this thinning forms a cross section parallel to both the longitudinal direction and the thickness direction of the magnetic recording medium 10. The obtained thin sample is observed by a transmission electron microscope (H-9500 manufactured by Hitachi High-Technologies Corporation) at an acceleration voltage of 200 kV and a total magnification of 500,000 times so that the entire magnetic layer 13 is included in the thickness direction of the magnetic layer 13, and a TEM photograph is taken. Next, 50 particles are randomly selected from the TEM photograph, and the long axis length DL and short axis length DS of each particle are measured. Here, the long axis length DL means the maximum distance between two parallel lines drawn from all angles so as to be tangent to the contour of each particle (so-called maximum Feret diameter). On the other hand, the minor axis length DS means the maximum length of the particle in a direction perpendicular to the major axis length DL of the particle.

[0053] Next, the long axis lengths DL of the 50 measured particles are simply averaged (arithmetic mean) to determine the average long axis length DLave. The average long axis length DLave thus determined is the average particle size of the magnetic powder. The short axis lengths DS of the 50 measured particles are also simply averaged (arithmetic mean) to determine the average short axis length DSave. The average aspect ratio of the particles (DLave / DSave) is then calculated from the average long axis length DLave and the average short axis length DSave.

[0054] The average particle volume of the magnetic powder is preferably 5500 nm 3 Less than or equal to 270 nm, more preferably 3 More than 5500nm 3 Less than or equal to 900 nm, and even more preferably 3 More than 5500nm 3 The average particle volume of the magnetic powder is 5500 nm or less. 3 When the average particle size of the magnetic powder is 22 nm or less, the same effect as when the average particle volume of the magnetic powder is 270 nm or less can be obtained. 3If the average particle size of the magnetic powder is 8 nm or more, the same effect as in the case where the average particle size of the magnetic powder is 8 nm or more can be obtained.

[0055] When the ε iron oxide particles 20 are spherical or nearly spherical, the average particle volume of the magnetic powder is calculated as follows. First, the average major axis length DLave is calculated in the same manner as in the above-mentioned method for calculating the average particle size of the magnetic powder. Next, the average volume V of the magnetic powder is calculated by the following formula. V = (π / 6) × (DLave) 3

[0056] (Binding agent) As the binder, a resin having a structure in which a crosslinking reaction is given to a polyurethane resin, a vinyl chloride resin, or the like is preferable. However, the binder is not limited to these, and other resins may be appropriately blended depending on the physical properties required for the magnetic recording medium 10. There is no particular limitation on the resin to be blended, so long as it is a resin that is generally used in coating-type magnetic recording media 10.

[0057] Examples of the polymer include polyvinyl chloride, polyvinyl acetate, vinyl chloride-vinyl acetate copolymer, vinyl chloride-vinylidene chloride copolymer, vinyl chloride-acrylonitrile copolymer, acrylic acid ester-acrylonitrile copolymer, acrylic acid ester-vinyl chloride-vinylidene chloride copolymer, vinyl chloride-acrylonitrile copolymer, acrylic acid ester-acrylonitrile copolymer, acrylic acid ester-vinylidene chloride copolymer, methacrylic acid ester-vinylidene chloride copolymer, methacrylic acid ester-vinyl chloride copolymer, methacrylic acid ester-ethylene copolymer, polyvinyl fluoride, vinylidene chloride-acrylonitrile copolymer, acrylonitrile-butadiene copolymer, polyamide resin, polyvinyl butyral, cellulose derivatives (cellulose acetate butyrate, cellulose diacetate, cellulose triacetate, cellulose propionate, nitrocellulose), styrene-butadiene copolymer, polyester resin, amino resin, and synthetic rubber.

[0058] Examples of the thermosetting resin or reactive resin include phenol resin, epoxy resin, urea resin, melamine resin, alkyd resin, silicone resin, polyamine resin, and urea formaldehyde resin.

[0059] Furthermore, in order to improve the dispersibility of the magnetic powder, polar functional groups such as -SO3M, -OSO3M, -COOM, and P=O(OM)2 may be introduced into each of the above-mentioned binders. Here, M in the above chemical formula is a hydrogen atom or an alkali metal such as lithium, potassium, or sodium.

[0060] Furthermore, the polar functional groups include -NR1R2, -NR1R2R3 + X - Side chain type with terminal group of >NR1R2 + X - In the above formula, R1, R2, and R3 are hydrogen atoms or hydrocarbon groups, and X - is a halogen element ion such as fluorine, chlorine, bromine, or iodine, or an inorganic or organic ion. Examples of the polar functional group include -OH, -SH, -CN, and an epoxy group.

[0061] (Lubricant) The lubricant contained in the magnetic layer 13 contains, for example, a fatty acid and a fatty acid ester. The fatty acid contained in the lubricant is, for example, a compound represented by the following general formula: <1> and compounds represented by the general formula <2> In addition, the fatty acid ester contained in the lubricant preferably contains at least one of the compounds represented by the following general formula: <3> and compounds represented by the general formula <4> It is preferred that the lubricant contains at least one of the compounds represented by the general formula: <1> and compounds represented by the general formula <3> By including two kinds of compounds represented by the general formula <2> and compounds represented by the general formula <3> By including two kinds of compounds represented by the general formula <1> and compounds represented by the general formula <4> By including two kinds of compounds represented by the general formula <2> and compounds represented by the general formula <4> By including two kinds of compounds represented by the general formula <1> Compounds represented by the general formula <2> and compounds represented by the general formula <3> By including three kinds of compounds represented by the general formula <1> Compounds represented by the general formula <2> and compounds represented by the general formula <4> By including three kinds of compounds represented by the general formula <1> Compounds represented by the general formula <3> and compounds represented by the general formula <4> By including three kinds of compounds represented by the general formula <2> Compounds represented by the general formula <3> and compounds represented by the general formula <4> or by including three kinds of compounds represented by the general formula <1> Compounds represented by the general formula <2> Compounds represented by the general formula <3> and compounds represented by the general formula <4> By containing these four compounds, it is possible to suppress an increase in the dynamic friction coefficient due to repeated recording or reproduction on the magnetic recording medium 10. As a result, the running properties of the magnetic recording medium 10 can be further improved. CH3(CH2) n COOH… <1> (However, the above general formula <1> In the formula, n is an integer selected from the range of 14 to 22. CH3(CH2) p COO(CH2) q CH3… <2> (However, the above general formula <2> In the formula, p is an integer selected from the range of 14 to 22, and q is an integer selected from the range of 2 to 5. CH3(CH2) n CH=CH(CH2) m COOH… <3> (However, the above general formula <3> In the formula, n+m is an integer selected from the range of 12 to 20. CH3(CH2) p COO-(CH2) q CH(CH3)2… <4> (However, the above general formula <4> In the formula, p is an integer selected from the range of 14 to 22, and q is an integer selected from the range of 1 to 3.

[0062] (Additives) The magnetic layer 13 may further contain non-magnetic reinforcing particles such as aluminum oxide (α, β or γ alumina), chromium oxide, silicon oxide, diamond, garnet, emery, boron nitride, titanium carbide, silicon carbide, titanium carbide, titanium oxide (rutile or anatase titanium oxide), etc.

[0063] (base layer 12) The underlayer 12 is a non-magnetic layer containing a non-magnetic powder and a binder. The underlayer 12 may further contain at least one additive selected from the group consisting of a lubricant, conductive particles, a hardener, and an anti-rust agent, as necessary. The underlayer 12 may have a multi-layer structure in which a plurality of layers are laminated. The average thickness of the underlayer 12 is preferably 0.5 μm or more and 0.9 μm or less, more preferably 0.6 μm or more and 0.7 μm or less. By reducing the average thickness of the underlayer 12 to 0.9 μm or less, the Young's modulus of the entire magnetic recording medium 10 is effectively reduced compared to the case where the thickness of the base 11 is reduced. This makes it easier to control the tension of the magnetic recording medium 10. In addition, by making the average thickness of the underlayer 12 0.5 μm or more, the adhesive force between the base 11 and the underlayer 12 is ensured. In addition, the variation in thickness of the underlayer 12 can be suppressed, and the roughness of the surface 13S of the magnetic layer 13 can be prevented from increasing.

[0064] The average thickness of the underlayer 12 can be obtained, for example, as follows. First, a magnetic recording medium 10 with a width of 1 / 2 inch is prepared, and cut into a length of 250 mm to prepare a sample. Next, the underlayer 12 and the magnetic layer 13 are peeled off from the substrate 11 for the sample magnetic recording medium 10. Next, a Mitutoyo Laser Hologram (LGH-110C) is used as a measuring device to measure the thickness of the laminate of the underlayer 12 and the magnetic layer 13 peeled off from the substrate 11 at five or more positions. After that, the measured values ​​are simply averaged (arithmetic averaged) to calculate the average thickness of the laminate of the underlayer 12 and the magnetic layer 13. The measurement positions are selected randomly from the sample. Finally, the average thickness of the underlayer 12 is obtained by subtracting the average thickness of the magnetic layer 13 measured using the TEM as described above from the average thickness of the laminate.

[0065] The underlayer 12 may have pores, that is, the underlayer 12 may have a large number of pores. The pores of the underlayer 12 may be formed, for example, by forming pores (pores 13A) in the magnetic layer 13, and in particular, may be formed by pressing a large number of protrusions provided on the surface 14S of the back layer 14 of the magnetic recording medium 10 against the magnetic layer side surface. That is, pores may be formed in the magnetic layer 13 and the underlayer 12 by forming recesses corresponding to the shape of the protrusions on the surface 13S of the magnetic layer 13. The pores may also be formed by volatilization of the solvent in the drying process of the magnetic layer forming paint. In addition, when the magnetic layer forming paint is applied to the surface of the underlayer 12 to form the magnetic layer 13, the solvent in the magnetic layer forming paint may pass through the pores of the underlayer 12 formed when the underlayer is applied and dried, and penetrate into the underlayer 12. Thereafter, when the solvent that has penetrated into the underlayer 12 volatilizes during the drying process of the magnetic layer 13, the solvent that has penetrated into the underlayer 12 may move from the underlayer 12 to the surface 13S of the magnetic layer 13, thereby forming pores. The pores thus formed may, for example, communicate with the magnetic layer 13 and the underlayer 12. The average diameter of the pores can be adjusted by changing the solid content or type of solvent of the paint for forming the magnetic layer and / or the drying conditions of the paint for forming the magnetic layer. By forming pores in both the magnetic layer 13 and the underlayer 12, a particularly suitable amount of lubricant for good running stability appears on the magnetic layer side surface, and the increase in the dynamic friction coefficient due to repeated recording or reproduction can be further suppressed.

[0066] From the viewpoint of suppressing a decrease in the dynamic friction coefficient after repeated recording or reproduction, it is preferable that the holes in the underlayer 12 are connected to the holes 13A in the magnetic layer 13. Here, the fact that the holes in the underlayer 12 are connected to the holes 13A in the magnetic layer 13 includes a state in which some of the many holes in the underlayer 12 are connected to some of the many holes 13A in the magnetic layer 13.

[0067] From the viewpoint of improving the supply of lubricant to the surface 13S of the magnetic layer 13, it is preferable that the numerous holes include some extending in a direction perpendicular to the surface 13S of the magnetic layer 13. Also, from the viewpoint of improving the supply of lubricant to the surface 13S of the magnetic layer 13, it is preferable that the holes of the underlayer 12 extending in a direction perpendicular to the surface 13S of the magnetic layer 13 and the holes 13A of the magnetic layer 13 extending in a direction perpendicular to the surface 13S of the magnetic layer 13 are connected to each other.

[0068] (Non-magnetic powder in underlayer 12) The non-magnetic powder includes at least one of inorganic particle powder and organic particle powder. The non-magnetic powder may also include carbon powder such as carbon black. One type of non-magnetic powder may be used alone, or two or more types of non-magnetic powder may be used in combination. The inorganic particles include, for example, metals, metal oxides, metal carbonates, metal sulfates, metal nitrides, metal carbides, or metal sulfides. The shape of the non-magnetic powder may be, for example, various shapes such as needle-like, spherical, cubic, and plate-like, but is not limited thereto.

[0069] (Binding agent for base layer 12) The binder in the underlayer 12 is the same as that in the magnetic layer 13 described above.

[0070] (Back layer 14) The back layer 14 contains, for example, a binder and a nonmagnetic powder. The back layer 14 may further contain at least one additive selected from the group consisting of a lubricant, a hardener, and an antistatic agent, as necessary. The binder and nonmagnetic powder in the back layer 14 are the same as those in the underlayer 12 described above.

[0071] The average particle size of the non-magnetic powder in the back layer 14 is preferably 10 nm or more and 150 nm or less, more preferably 15 nm or more and 110 nm or less. The average particle size of the non-magnetic powder in the back layer 14 is determined in the same manner as the average particle size of the magnetic powder in the magnetic layer 13. The non-magnetic powder may include powder having two or more particle size distributions.

[0072] The upper limit of the average thickness of the back layer 14 is preferably 0.6 μm or less, and particularly preferably 0.5 μm or less. If the upper limit of the average thickness of the back layer 14 is 0.6 μm or less, the thickness of the underlayer 12 and the base 11 can be kept thick even when the average thickness of the magnetic recording medium 10 is 5.6 μm or less, so that the running stability of the magnetic recording medium 10 in a recording and reproducing device can be maintained. The lower limit of the average thickness of the back layer 14 is not particularly limited, but is, for example, 0.2 μm or more, and particularly preferably 0.3 μm or more.

[0073] The average thickness of the back layer 14 is obtained as follows. First, a magnetic recording medium 10 having a width of 1 / 2 inch is prepared and cut into a length of 250 mm to prepare a sample. Next, the thickness of the sample magnetic recording medium 10 is measured at five or more points using a Mitutoyo Laser Hologram (LGH-110C) as a measuring device, and the measured values ​​are simply averaged (arithmetic average) to obtain the average thickness t T [μm] is calculated. Note that the measurement positions are selected randomly from the sample. Next, the back layer 14 is removed from the sample magnetic recording medium 10 with a solvent such as MEK (methyl ethyl ketone) or dilute hydrochloric acid. After that, the above-mentioned laser hologram is used again to measure the thickness of the sample from which the back layer 14 has been removed from the magnetic recording medium 10 at five or more points, and the measured values ​​are simply averaged (arithmetic averaged) to obtain the average thickness t B [μm] is calculated. The measurement positions are selected randomly from the sample. Finally, the average thickness t of the back layer 14 is calculated from the following formula: b Calculate [μm]. t b [μm]=t T [μm]-t B [μm]

[0074] 1, the back layer 14 has a surface on which a large number of protrusions 14A are provided. The large number of protrusions 14A are intended to form a large number of holes 13A on the surface 13S of the magnetic layer 13 when the magnetic recording medium 10 is wound into a roll. The large number of holes 13A are formed, for example, by a large number of nonmagnetic particles protruding from the surface of the back layer 14.

[0075] (Average thickness of magnetic recording medium 10) The upper limit of the average thickness (average total thickness) of the magnetic recording medium 10 is preferably 5.6 μm or less, more preferably 5.2 μm or less, particularly preferably 4.8 μm or less, and even more preferably 4.4 μm or less. When the average thickness of the magnetic recording medium 10 is 5.6 μm or less, the recording capacity that can be recorded in one data cartridge can be increased compared to that of a general magnetic recording medium. The lower limit of the average thickness of the magnetic recording medium 10 is not particularly limited, but is, for example, 3.5 μm or more.

[0076] The average thickness tT of the magnetic recording medium 10 is found as follows. First, a magnetic recording medium 10 with a width of 1 / 2 inch is prepared, and then cut into a length of 250 mm to prepare a sample. Next, using a Mitutoyo Laser Hologram (LGH-110C) as a measuring device, the thickness of the sample is measured at five or more positions, and the measured values ​​are simply averaged (arithmetic mean) to calculate the average value tT [μm]. Note that the measurement positions are selected randomly from the sample.

[0077] (Coercive force Hc) The upper limit of the coercive force Hc in the longitudinal direction of the magnetic recording medium 10 is preferably 2000 Oe or less, more preferably 1900 Oe or less, and even more preferably 1800 Oe or less. When the coercive force Hc2 in the longitudinal direction is 2000 Oe or less, the magnetization reacts sensitively to the perpendicular magnetic field from the recording head, and therefore a good recording pattern can be formed.

[0078] The lower limit of the coercive force Hc measured in the longitudinal direction of the magnetic recording medium 10 is preferably 1000 Oe or more. If the lower limit of the coercive force Hc in the longitudinal direction is 1000 Oe or more, demagnetization due to leakage flux from the recording head can be suppressed.

[0079] The coercive force Hc is obtained as follows. Three magnetic recording media 10 are stacked and bonded with double-sided tape, and then punched out with a φ6.39 mm punch to create a measurement sample. At this time, marking is performed with any non-magnetic ink so that the longitudinal direction (running direction) of the magnetic recording medium can be identified. Then, the MH loop of the measurement sample (whole magnetic recording medium 10) corresponding to the longitudinal direction (running direction of magnetic recording medium 10) of the magnetic recording medium 10 is measured using a vibrating sample magnetometer (VSM). Next, the coating film (underlayer 12, magnetic layer 13, back layer 14, etc.) is wiped off with acetone or ethanol, etc., leaving only the substrate 11. Then, three obtained substrates 11 are stacked and bonded with double-sided tape, and then punched out with a φ6.39 mm punch to obtain a sample for background correction (hereinafter simply referred to as a correction sample). Thereafter, the MH loop of the correction sample (substrate 11) corresponding to the longitudinal direction of the substrate 11 (the running direction of the magnetic recording medium 10) is measured using the VSM.

[0080] The MH loop of the measurement sample (whole magnetic recording medium 10) and the MH loop of the correction sample (substrate 11) are measured using, for example, a high-sensitivity vibration sample magnetometer "VSM-P7-15 type" manufactured by Toei Kogyo Co., Ltd. The measurement conditions are as follows: measurement mode: full loop, maximum magnetic field: 15 kOe, magnetic field step: 40 bits, time constant of locking amp: 0.3 sec, waiting time: 1 sec, number of MH averages: 20.

[0081] After obtaining the two MH loops, background correction is performed by subtracting the MH loop of the correction sample (substrate 11) from the MH loop of the measurement sample (whole magnetic recording medium 10), and the MH loop after background correction is obtained. For the calculation of this background correction, a measurement and analysis program attached to the "VSMP7-15 type" is used.

[0082] The coercive force Hc is obtained from the obtained MH loop after background correction. For this calculation, a measurement and analysis program attached to the "VSM-P7-15 type" is used. All of the above MH loop measurements are performed at 25°C. Furthermore, no "demagnetizing field correction" is performed when measuring the MH loop in the longitudinal direction of the magnetic recording medium 10.

[0083] (Square ratio) The squareness ratio S1 in the perpendicular direction (thickness direction) of the magnetic recording medium 10 is, for example, 65% or more, preferably 70% or more, more preferably 75% or more, even more preferably 80% or more, and particularly preferably 85% or more. When the squareness ratio S1 is 65% or more, the perpendicular orientation of the magnetic powder is sufficiently high, and therefore a better SNR can be obtained.

[0084] The squareness ratio S1 is obtained as follows. Three magnetic recording media 10 are stacked and bonded with double-sided tape, and then punched out with a φ6.39 mm punch to create a measurement sample. At this time, marking is performed with any non-magnetic ink so that the longitudinal direction (running direction) of the magnetic recording medium can be identified. Then, the MH loop of the measurement sample (whole magnetic recording medium 10) corresponding to the longitudinal direction (running direction of magnetic recording medium 10) of the magnetic recording medium 10 is measured using a vibrating sample magnetometer (VSM). Next, the coating film (underlayer 12, magnetic layer 13, back layer 14, etc.) is wiped off with acetone or ethanol, etc., leaving only the substrate 11. Then, three obtained substrates 11 are stacked and bonded with double-sided tape, and then punched out with a φ6.39 mm punch to obtain a sample for background correction (hereinafter simply referred to as a correction sample). Thereafter, the MH loop of the correction sample (substrate 11) corresponding to the longitudinal direction of the substrate 11 (the running direction of the magnetic recording medium 10) is measured using the VSM.

[0085] The MH loop of the measurement sample (whole magnetic recording medium 10) and the MH loop of the correction sample (substrate 11) are measured using, for example, a high-sensitivity vibration sample magnetometer "VSM-P7-15 type" manufactured by Toei Kogyo Co., Ltd. The measurement conditions are as follows: measurement mode: full loop, maximum magnetic field: 15 kOe, magnetic field step: 40 bits, time constant of locking amp: 0.3 sec, waiting time: 1 sec, number of MH averages: 20.

[0086] After obtaining the two MH loops, background correction is performed by subtracting the MH loop of the correction sample (substrate 11) from the MH loop of the measurement sample (whole magnetic recording medium 10), and the MH loop after background correction is obtained. For the calculation of this background correction, a measurement and analysis program attached to the "VSMP7-15 type" is used.

[0087] The saturation magnetization Ms (emu) and residual magnetization Mr (emu) of the obtained MH loop after background correction are substituted into the following equation to calculate the squareness ratio S1 (%). Squareness ratio S1(%)=(Mr / Ms)×100 It should be noted that all of the above MH loop measurements are performed at 25° C. Furthermore, when measuring the MH loop in the perpendicular direction to the magnetic recording medium 10, no “demagnetizing field correction” is performed.

[0088] The squareness ratio S2 in the longitudinal direction (running direction) of the magnetic recording medium 10 is preferably 35% or less, more preferably 30% or less, even more preferably 25% or less, particularly preferably 20% or less, and most preferably 15% or less. When the squareness ratio S2 is 35% or less, the magnetic powder has a sufficiently high vertical orientation, so that a better SNR can be obtained.

[0089] The squareness ratio S2 is determined in the same manner as the squareness ratio S1, except that the MH loop is measured in the longitudinal direction (traveling direction) of the magnetic recording medium 10 and the substrate 11.

[0090] (Activation volume Vact) The activation volume Vact is preferably 8000 nm 3 Less than 6000 nm, more preferably 3 Less than or equal to 5000 nm, and even more preferably less than 5000 nm 3 Below 4000 nm, particularly preferably 3 Below 3000 nm, most preferably 3 The activation volume Vact is 8000 nm 3 If the magnetic powder is dispersed in a good state, the bit inversion region can be made steep, and the magnetic signal recorded on the adjacent track can be prevented from being deteriorated by the leakage magnetic field from the recording head, resulting in a better SNR.

[0091] The activation volume Vact is calculated by the following formula derived by Street & Woolley. Vact(nm 3)=kB×T×Χirr / (μ0×Ms×S) (where kB is the Boltzmann constant (1.38×10 -23 J / K), T: temperature (K), Χirr: irreversible magnetic susceptibility, μ0: vacuum permeability, S: magnetorheological coefficient, Ms: saturation magnetization (emu / cm 3 ))

[0092] The irreversible magnetic susceptibility Χirr, saturation magnetization Ms, and magnetic viscosity coefficient S substituted in the above formula are obtained using VSM as follows. The measurement sample used in VSM is prepared by punching out three magnetic recording media 10 stacked with double-sided tape using a φ6.39 mm punch. At this time, marking is performed with any non-magnetic ink so that the longitudinal direction (running direction) of the magnetic recording medium 10 can be identified. The measurement direction by VSM is the thickness direction (vertical direction) of the magnetic recording medium 10. Furthermore, the measurement by VSM is performed at 25°C on a measurement sample cut out from a long magnetic recording medium 10. Furthermore, "demagnetization field correction" is not performed when measuring the MH loop in the thickness direction (vertical direction) of the magnetic recording medium 10. Furthermore, a high-sensitivity vibration sample magnetometer "VSM-P7-15 type" manufactured by Toei Kogyo Co., Ltd. is used to measure the MH loop of the measurement sample (the entire magnetic recording medium 10) and the MH loop of the correction sample (substrate 11). The measurement conditions were as follows: measurement mode: full loop, maximum magnetic field: 15 kOe, magnetic field step: 40 bits, time constant of locking amp: 0.3 sec, waiting time: 1 sec, number of MH averages: 20.

[0093] (irreversible magnetic susceptibility Χirr) The irreversible magnetic susceptibility Χirr is defined as the slope of the remanent magnetization curve (DCD curve) near the remanent coercivity Hr. First, a magnetic field of -1193 kA / m (15 kOe) is applied to the entire magnetic recording medium 10, and the magnetic field is returned to zero to create a remanent magnetization state. Then, a magnetic field of about 15.9 kA / m (200 Oe) is applied in the opposite direction, and the magnetic field is returned to zero again to measure the amount of remanent magnetization. After that, a magnetic field 15.9 kA / m larger than the previous applied magnetic field is applied, and the measurement is repeated to return the magnetic field to zero. The remanent magnetization is plotted against the applied magnetic field to measure the DCD curve. From the obtained DCD curve, the point where the magnetization amount is zero is taken as the remanent coercivity Hr, and the DCD curve is differentiated to determine the slope of the DCD curve for each magnetic field. The slope of this DCD curve near the remanent coercivity Hr is the slope of the DCD curve.

[0094] (Saturation magnetization Ms) First, a background-corrected MH loop is obtained in the same manner as in the above-mentioned method for measuring the coercive force Hc. Next, the value of the saturation magnetization Ms(emu) of the obtained MH loop and the volume (cm 3 ) to Ms(emu / cm 3 ) is calculated. The volume of the magnetic layer 13 is found by multiplying the area of ​​the measurement sample by the average thickness of the magnetic layer 13. The method for calculating the average thickness of the magnetic layer 13, which is necessary for calculating the volume of the magnetic layer 13, is as described above.

[0095] (Magnetic viscosity coefficient S) First, a magnetic field of -1193 kA / m (15 kOe) is applied to the entire magnetic recording medium 10 (measurement sample), and the magnetic field is returned to zero to create a state of residual magnetization. After that, a magnetic field equivalent to the value of the residual coercivity Hr obtained from the DCD curve is applied in the opposite direction. With the magnetic field applied, the amount of magnetization is continuously measured at regular time intervals for 1000 seconds. The magnetic viscosity coefficient S is calculated by referring to the relationship between time t and amount of magnetization M(t) obtained in this way according to the following formula. M(t) = M0 + S × ln(t) (where M(t) is the amount of magnetization at time t, M0 is the initial amount of magnetization, S is the magnetic viscosity coefficient, and ln(t) is the natural logarithm of time.)

[0096] (Friction coefficient ratio (μ B / μ A )) The magnetic recording medium 10 preferably has a dynamic friction coefficient μ between the surface 13S of the magnetic layer 13 of the magnetic recording medium 10 and the magnetic head when a tension of 0.4 N is applied in the longitudinal direction of the magnetic recording medium 10. A and the dynamic friction coefficient μ between the surface 13S of the magnetic layer 13 of the magnetic recording medium 100 and the magnetic head when a tension of 1.2 N is applied to the magnetic recording medium 10 in the longitudinal direction. B Friction coefficient ratio (μ B / μ A ) is 1.0 or more and 2.0 or less, more preferably 1.0 or more and 1.8 or less, and even more preferably 1.0 or more and 1.6 or less. B / μ A ) within the above range can reduce the change in the dynamic friction coefficient due to tension fluctuations during running, thereby stabilizing the running of the magnetic recording medium 10.

[0097] The dynamic friction coefficients μA and μB for calculating the friction coefficient ratio (μB / μA) are found as follows. First, as shown in Fig. 8, a 1 / 2 inch wide magnetic recording medium 10 is placed on two cylindrical guide rolls 91, 92 with a diameter of 1 inch that are arranged parallel to each other and spaced apart from each other so that the surface 13S of the magnetic layer 13 comes into contact with them. The positional relationship between the two guide rolls 91, 92 is fixed.

[0098] Next, the magnetic recording medium 10 is brought into contact with a head block (for recording and reproducing) 93 mounted on an LTO5 drive so that the surface 13S of the magnetic layer 13 is in contact and the embrace angle θ1 [°] is 5.6°, and one end of the magnetic recording medium 10 is held by a gripping jig 94 and connected to a movable strain gauge 95, while a weight 96 is hung from the other end of the magnetic recording medium 10 to apply a tension T0 of 0.4 N. The head block 93 is fixed at a position where the embrace angle θ1 [°] is 5.6°. This also fixes the positional relationship between the guide rolls 91, 92 and the head block 93.

[0099] Next, the magnetic recording medium 10 is caused to slide 60 mm toward the movable strain gauge 95 at a speed of 10 mm / s relative to the head block 93 by the movable strain gauge 95. The output value (voltage) of the movable strain gauge 95 during this sliding is converted to T[N] based on the linear relationship between the output value and the load that has been acquired in advance (described later). T[N] is acquired 13 times from the start of the 60 mm sliding to the end of the sliding, and the 11 T[N]s excluding the first and last two times are simply averaged to obtain T ave [N] is obtained. Then, the coefficient of dynamic friction μ A Request.

number

[0100] The linear relationship described above is obtained as follows. That is, the output value (voltage) of the movable strain gauge 95 is obtained when a load of 0.4 N and a load of 1.5 N are applied to the movable strain gauge 95. From the obtained two output values ​​and the two loads, a linear relationship between the output value and the load is obtained. Using this linear relationship, the output value (voltage) by the movable strain gauge 95 during sliding is converted to T [N] as described above.

[0101] Dynamic friction coefficient μ B The coefficient of dynamic friction μ is the same as that of the tension T0 [N] applied to the other end of the A It is measured in the same manner as the measurement of . The dynamic friction coefficient μ measured as above A and the coefficient of dynamic friction μ B From the above, the friction coefficient ratio (μ B / μ A ) is calculated.

[0102] If the dynamic friction coefficient between the surface 13S of the magnetic layer 13 and the magnetic head when the tension applied to the magnetic recording medium 10 is 0.6 N is μC, the friction coefficient ratio (μC(1000) / μC(5)) between the dynamic friction coefficient μC(5) at the 5th time from the start of running and the dynamic friction coefficient μC(1000) at the 1000th time from the start of running is preferably 1.0 to 2.0, more preferably 1.2 to 1.8. If the friction coefficient ratio (μC(1000) / μC(5)) is 1.0 to 2.0, the change in the dynamic friction coefficient due to multiple runs can be reduced, and the running of the magnetic recording medium 10 can be stabilized. Here, the magnetic head used is one that is compatible with the magnetic recording medium 10.

[0103] (Friction coefficient ratio (μ C(1000) / μ C(5) )) The kinetic friction coefficient μC(5) and the kinetic friction coefficient μC(1000) for calculating the friction coefficient ratio (μC(1000) / μC(5)) can be calculated as follows.

[0104] The magnetic recording medium 10 is preferably subjected to a tension of 0.6 N in the longitudinal direction and is caused to reciprocate five times over a magnetic head, and the dynamic friction coefficient μ C(5) and the dynamic friction coefficient μ at the 1000th reciprocation when the magnetic head is reciprocated 1000 times. C(1000) Friction coefficient ratio (μ C(1000) / μ C(5) ) is 1.0 to 2.0, more preferably 1.0 to 1.8, and even more preferably 1.0 to 1.6. C(1000) / μ C(5) ) within the above range can reduce the change in the dynamic friction coefficient due to multiple runs, thereby stabilizing the running of the magnetic recording medium 10.

[0105] Friction coefficient ratio (μ C(1000) / μ C(5) ) to calculate the dynamic friction coefficient μ C(5) and the coefficient of dynamic friction μ C(1000) is calculated as follows: The coefficient of dynamic friction μ A The magnetic recording medium 10 is connected to the movable strain gauge 71 in the same manner as in the measurement method of . Then, the magnetic recording medium 10 is caused to slide 60 mm toward the movable strain gauge (forward path) and 60 mm away from the movable strain gauge (return path) at 10 mm / s relative to the head block 74. This back-and-forth movement is repeated 1000 times. Of these 1000 back-and-forth movements, the output value (voltage) of the strain gauge is obtained 13 times from the start of the 60 mm sliding on the fifth outward path to the end of the sliding, and the dynamic friction coefficient μ A Based on the linear relationship between the output value and the load (described later), it is converted to T [N]. The simple average of 11 values ​​excluding the first and last two is taken to obtain T ave [N] is calculated using the following formula: C(5) Request.

number

[0106] [1-2 Manufacturing method of magnetic recording medium 10] Next, a method for manufacturing the magnetic recording medium 10 having the above-mentioned configuration will be described. First, a paint for forming the undercoat layer is prepared by kneading and dispersing non-magnetic powder, binder, lubricant, etc. in a solvent. Next, a paint for forming the magnetic layer is prepared by kneading and dispersing magnetic powder, binder, lubricant, etc. in a solvent. Next, a paint for forming the back layer is prepared by kneading and dispersing binder, non-magnetic powder, etc. in a solvent. For example, the following solvents, dispersing devices, and kneading devices can be used to prepare the paint for forming the magnetic layer, the paint for forming the undercoat layer, and the paint for forming the back layer.

[0107] Examples of the solvent used in preparing the coating material include ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, alcohol-based solvents such as methanol, ethanol, and propanol, ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, propyl acetate, ethyl lactate, and ethylene glycol acetate, ether-based solvents such as diethylene glycol dimethyl ether, 2-ethoxyethanol, tetrahydrofuran, and dioxane, aromatic hydrocarbon-based solvents such as benzene, toluene, and xylene, and halogenated hydrocarbon-based solvents such as methylene chloride, ethylene chloride, carbon tetrachloride, chloroform, and chlorobenzene. These may be used alone or in appropriate mixture.

[0108] Examples of the kneading device used in the preparation of the above-mentioned coating material include, but are not limited to, a continuous twin-screw kneader, a continuous twin-screw kneader capable of diluting in multiple stages, a kneader, a pressure kneader, a roll kneader, etc. Examples of the dispersing device used in the preparation of the above-mentioned coating material include, but are not limited to, a roll mill, a ball mill, a horizontal sand mill, a vertical sand mill, a spike mill, a pin mill, a tower mill, a pearl mill (for example, "DCP Mill" manufactured by Eirich Co., Ltd.), a homogenizer, an ultrasonic dispersing machine, etc.

[0109] Next, the underlayer forming paint is applied to one main surface 11A of the substrate 11 and dried to form the underlayer 12. Next, the magnetic layer forming paint is applied to the underlayer 12 and dried to form the magnetic layer 13 on the underlayer 12. During drying, it is preferable to magnetically orient the magnetic powder in the thickness direction of the substrate 11, for example, by a solenoid coil. Also, during drying, the magnetic powder may be magnetically oriented in the running direction (longitudinal direction) of the substrate 11, and then magnetically oriented in the thickness direction of the substrate 11, for example, by a solenoid coil. By performing such magnetic field orientation treatment, the degree of vertical orientation (i.e., squareness ratio S1) of the magnetic powder can be improved. After the magnetic layer 13 is formed, the back layer forming paint is applied to the other main surface 11B of the substrate 11 and dried to form the back layer 14. This results in a magnetic recording medium 10.

[0110] The squareness ratios S1 and S2 are set to desired values ​​by, for example, adjusting the strength of the magnetic field applied to the coating film of the magnetic layer forming paint, the concentration of the solid content in the magnetic layer forming paint, and the drying conditions (drying temperature and drying time) of the coating film of the magnetic layer forming paint. The strength of the magnetic field applied to the coating film is preferably at least twice the coercive force of the magnetic powder. In order to further increase the squareness ratio S1 (i.e., to further reduce the squareness ratio S2), it is preferable to improve the dispersion state of the magnetic powder in the magnetic layer forming paint. In addition, in order to further increase the squareness ratio S1, it is also effective to magnetize the magnetic powder before the magnetic layer forming paint enters an orientation device for magnetic field orientation of the magnetic powder. The above-mentioned methods for adjusting the squareness ratios S1 and S2 may be used alone or in combination of two or more.

[0111] The obtained magnetic recording medium 10 is then subjected to a calendaring process to smooth the surface 13S of the magnetic layer 13. Next, the calendared magnetic recording medium 10 is wound into a roll, and in this state, the magnetic recording medium 10 is subjected to a heat treatment to transfer the numerous protrusions 14A on the surface of the back layer 14 to the surface 13S of the magnetic layer 13. As a result, numerous holes 13A are formed on the surface 13S of the magnetic layer 13.

[0112] The heat treatment temperature is preferably 50° C. or higher and 80° C. or lower. When the heat treatment temperature is 50° C. or higher, good transferability can be obtained. On the other hand, when the heat treatment temperature is 80° C. or higher, the amount of pores becomes too large, and there is a risk of an excess of lubricant on the surface 13S of the magnetic layer 13. Here, the heat treatment temperature is the temperature of the atmosphere in which the magnetic recording medium 10 is held.

[0113] The heat treatment time is preferably 15 hours or more and 40 hours or less. When the heat treatment time is 15 hours or more, good transferability can be obtained. On the other hand, when the heat treatment time is 40 hours or less, a decrease in productivity can be suppressed.

[0114] Finally, the magnetic recording medium 10 is cut to a predetermined width (for example, 1 / 2 inch width). In this manner, the desired magnetic recording medium 10 is obtained.

[0115] In the above manufacturing method, the pores (holes 13A) are formed on the surface of the magnetic layer 13 by transferring a large number of protrusions 14A provided on the surface 14S of the back layer 14 to the surface 13S of the magnetic layer 13, but the method of forming the pores is not limited to this. For example, the pores may be formed on the surface 13S of the magnetic layer 13 by adjusting the type of solvent contained in the paint for forming the magnetic layer and / or adjusting the drying conditions of the paint for forming the magnetic layer. In addition, for example, in the process of drying the solvent of the paint for forming the magnetic layer, the pores may be formed due to uneven distribution of the solid matter and the solvent contained in the paint for forming the magnetic layer. In addition, in the process of applying the paint for forming the magnetic layer, the solvent contained in the paint for forming the magnetic layer may be absorbed into the base layer 12 through the pores of the base layer 12 formed when the lower layer was applied and dried. In the drying process after the application, the solvent moves from the base layer 12 through the magnetic layer 13, and thus pores communicating between the magnetic layer 13 and the base layer 12 may be formed.

[0116] [1-3 Configuration of recording / playback device 30] Next, with reference to FIG. 4, a configuration of a recording / reproducing device 30 that records information on the above-mentioned magnetic recording medium 10 and reproduces information from the above-mentioned magnetic recording medium 10 will be described.

[0117] The recording and reproducing device 30 has a configuration capable of adjusting the tension applied to the magnetic recording medium 10 in the longitudinal direction. The recording and reproducing device 30 also has a configuration capable of loading a magnetic recording medium cartridge 10A. For ease of explanation, the recording and reproducing device 30 will be described as having a configuration capable of loading one magnetic recording medium cartridge 10A. However, in the present disclosure, the recording and reproducing device 30 may also have a configuration capable of loading a plurality of magnetic recording medium cartridges 10A.

[0118] The recording / playback device 30 is connected to information processing devices such as a server 41 and a personal computer (hereinafter referred to as "PC") 42, for example, via a network 43, and is configured to be able to record data supplied from these information processing devices onto the magnetic recording medium cartridge 10A.

[0119] As shown in FIG. 4, the recording / playback device 30 includes a spindle 31, a reel 32, a drive unit 33, a drive unit 34, a plurality of guide rollers 35, a head unit 36, a communication interface (hereinafter referred to as I / F) 37, and a control device 38.

[0120] The spindle 31 is configured to be able to mount the magnetic recording medium cartridge 10A. The magnetic recording medium cartridge 10A is compliant with the LTO (Linear Tape Open) standard, and a single reel 10C around which the magnetic recording medium 10 is wound is rotatably housed in a cartridge case 10B. A V-shaped servo pattern is recorded in advance as a servo signal on the magnetic recording medium 10. The reel 32 is configured to be able to fix the tip of the magnetic recording medium 10 pulled out from the magnetic recording medium cartridge 10A.

[0121] The driving device 33 is a device that rotates the spindle 31. The driving device 34 is a device that rotates the reel 32. When recording or reproducing data on the magnetic recording medium 10, the driving devices 33 and 34 rotate the spindle 31 and the reel 32, respectively, to run the magnetic recording medium 10. The guide roller 35 is a roller for guiding the running of the magnetic recording medium 10.

[0122] The head unit 36 ​​includes a plurality of recording heads for recording data signals on the magnetic recording medium 10, a plurality of reproducing heads for reproducing the data signals recorded on the magnetic recording medium 10, and a plurality of servo heads for reproducing the servo signals recorded on the magnetic recording medium 10. As the recording heads, for example, a ring-type head can be used, and as the reproducing heads, for example, a magnetoresistive effect magnetic head can be used, but the types of the recording heads and reproducing heads are not limited to these.

[0123] The I / F 37 is for communicating with information processing devices such as a server 41 and a PC 42 , and is connected to a network 43 .

[0124] The control device 38 controls the entire recording / reproducing device 30. For example, in response to a request from the information processing device, such as the server 41 or the PC 42, the control device 38 records a data signal supplied from the information processing device on the magnetic recording medium 10 by the head unit 36. In addition, in response to a request from the information processing device, such as the server 41 or the PC 42, the control device 38 reproduces the data signal recorded on the magnetic recording medium 10 by the head unit 36, and supplies it to the information processing device.

[0125] [1-4 Effects] As described above, the magnetic recording medium 10 of the present embodiment is a tape-shaped member in which the substrate 11, the underlayer 12, and the magnetic layer 13 are laminated, and is designed to satisfy each of the following constituent requirements (1) to (8). (1) The substrate 11 contains polyester as a main component. (2) The average thickness of the underlayer 12 is 0.9 μm or less. (3) The underlayer 12 and the magnetic layer 13 contain a lubricant. (4) The magnetic layer 13 has a surface 13S in which a large number of holes 13A are formed, and the arithmetic mean roughness Ra of the surface 13S is 2.5 nm or less. (5) The overall BET specific surface area of ​​the magnetic recording medium 10 in a dry state after removing the lubricant is 3.5 m 2 / g or more. (6) The squareness ratio of the magnetic recording medium 10 in the perpendicular direction is 65% or more. (7) The average thickness of the magnetic layer 13 is 90 nm or less. (8) The average thickness of the magnetic recording medium 10 is 5.6 μm or less.

[0126] The magnetic recording medium 10 of the present embodiment has such a configuration, and even if the overall thickness is thin, the increase in the dynamic friction coefficient after repeated recording or reproduction can be suppressed. In addition, since the underlayer 12 is relatively thin, the material cost can be reduced, and the winding amount of the magnetic recording medium 10 that can be loaded into one magnetic recording medium cartridge 10A can be improved. Furthermore, since the thickness of the underlayer 12 relative to the thickness of the base 11 is reduced, the overall Young's modulus of the magnetic recording medium 10 can be reduced. Since the Young's modulus of the underlayer 12 containing non-magnetic powder and a binder is higher than that of the base 11 containing polyester as the main component, even if the thickness of the magnetic recording medium 10 remains unchanged, the base 11 becomes more dominant as a factor that determines the Young's modulus of the magnetic recording medium 10 by reducing the thickness of the underlayer 12 relative to the thickness of the base 11. Since the Young's modulus of the entire magnetic recording medium 10 can be reduced, when the magnetic recording medium 10 is run while tension is applied along its longitudinal direction, the responsiveness of the deformation of the magnetic recording medium 10 to the applied tension is improved. Therefore, when recording or reproducing is performed in the recording and reproducing device 30, the running stability of the magnetic recording medium 10 can be improved.

[0127] <2. Modifications> (Variation 1) In the above embodiment, the ε-iron oxide particles 20 ( FIG. 3 ) having the shell portion 22 with a two-layer structure have been described as an example, but the magnetic recording medium of the present technology may include the ε-iron oxide particles 20A having the shell portion 23 with a single-layer structure, as shown in, for example, FIG. 5 . The shell portion 23 in the ε-iron oxide particles 20A has a similar configuration to the first shell portion 22a, for example. However, from the viewpoint of suppressing deterioration of characteristics, the ε-iron oxide particles 20 having the shell portion 22 with a two-layer structure described in the above embodiment are more preferable than the ε-iron oxide particles 20A of Modification 1.

[0128] (Variation 2) In the magnetic recording medium 10 according to the embodiment described above, the ε iron oxide particles 20 having a core-shell structure have been described as an example, but the ε iron oxide particles may contain an additive instead of the core-shell structure, or may have a core-shell structure and contain an additive. In this case, a part of Fe in the ε iron oxide particles is replaced with the additive. By containing an additive in the ε iron oxide particles, the coercive force Hc of the ε iron oxide particles as a whole can be adjusted to a coercive force Hc suitable for recording, thereby improving ease of recording. The additive is a metal element other than iron, preferably a trivalent metal element, more preferably at least one of Al (aluminum), Ga (gallium) and In (indium), and even more preferably at least one of Al and Ga.

[0129] Specifically, the ε-iron oxide containing the additive is an ε-Fe2-xMxO3 crystal (wherein M is a metal element other than iron, preferably a trivalent metal element, more preferably at least one of Al, Ga, and In, and even more preferably at least one of Al and Ga. x is, for example, 0 <x<1である。)である。

[0130] (Variation 3) The magnetic powder of the present disclosure may contain a powder of nanoparticles containing hexagonal ferrite (hereinafter referred to as "hexagonal ferrite particles") instead of a powder of ε iron oxide particles. The hexagonal ferrite particles have, for example, a hexagonal plate shape or a nearly hexagonal plate shape. The hexagonal ferrite preferably contains at least one of Ba (barium), Sr (strontium), Pb (lead) and Ca (calcium), more preferably at least one of Ba and Sr. The hexagonal ferrite may specifically be, for example, barium ferrite or strontium ferrite. The barium ferrite may further contain at least one of Sr, Pb and Ca in addition to Ba. The strontium ferrite may further contain at least one of Ba, Pb and Ca in addition to Sr.

[0131] More specifically, hexagonal ferrite has the general formula MFe 12 O 19 The average composition is represented by the formula: where M is, for example, at least one metal selected from Ba, Sr, Pb, and Ca, and preferably at least one metal selected from Ba and Sr. M may be a combination of Ba and at least one metal selected from the group consisting of Sr, Pb, and Ca. M may also be a combination of Sr and at least one metal selected from the group consisting of Ba, Pb, and Ca. In the above general formula, a part of Fe may be substituted with another metal element.

[0132] When the magnetic powder contains a powder of hexagonal ferrite particles, the average particle size of the magnetic powder is preferably 50 nm or less, more preferably 40 nm or less, and even more preferably 30 nm or less. The average particle size of the magnetic powder is preferably 25 nm or less, 22 nm or less, 21 nm or less, or even more preferably 20 nm or less. The average particle size of the magnetic powder is, for example, 10 nm or more, preferably 12 nm or more, and more preferably 15 nm or more. Therefore, the average particle size of the magnetic powder containing the powder of hexagonal ferrite particles can be, for example, 10 nm or more to 50 nm or less, 10 nm or more to 40 nm or less, 12 nm or more to 30 nm or less, 12 nm or more to 25 nm or less, or 15 nm or more to 22 nm or less. When the average particle size of the magnetic powder is the above upper limit or less (for example, 50 nm or less, particularly 30 nm or less), good electromagnetic conversion characteristics (for example, SNR) can be obtained in the high recording density magnetic recording medium 10. When the average particle size of the magnetic powder is equal to or greater than the lower limit (eg, 10 nm or greater, preferably 12 nm or greater), the dispersibility of the magnetic powder is improved, and better electromagnetic conversion characteristics (eg, SNR) can be obtained.

[0133] When the magnetic powder contains a powder of hexagonal ferrite particles, the average aspect ratio of the magnetic powder may be preferably 1 to 3.5, more preferably 1 to 3.1, or 1.5 to 3.0, and even more preferably 1.8 to 2.8. By having the average aspect ratio of the magnetic powder within the above numerical range, it is possible to suppress the aggregation of the magnetic powder, and further, to suppress the resistance applied to the magnetic powder when the magnetic powder is vertically oriented in the process of forming the magnetic layer 13. This can lead to an improvement in the vertical orientation of the magnetic powder.

[0134] The average particle size and average aspect ratio of the magnetic powder containing the powder of hexagonal ferrite particles are obtained as follows. First, the magnetic recording medium 10 to be measured is processed and thinned by the FIB (Focused Ion Beam) method or the like. The thinning is performed along the length direction (longitudinal direction) of the magnetic tape. The obtained thin sample is observed in cross section in the thickness direction of the recording layer at an acceleration voltage of 200 kV and a total magnification of 500,000 times using a transmission electron microscope (H-9500 manufactured by Hitachi High-Technologies). Next, 50 particles that face the side toward the observation surface are selected from the TEM photograph taken, and the maximum plate thickness DA of each particle is measured. The maximum plate thicknesses DA thus obtained are simply averaged (arithmetic average) to obtain the average maximum plate thickness DAave. Next, the plate diameter DB of each magnetic powder is measured. Here, the plate diameter DB means the maximum distance between two parallel lines drawn from all angles so as to be tangent to the contour of the magnetic powder (so-called maximum Feret diameter). Next, the average plate diameter DBave is calculated by simply averaging (arithmetic mean) the measured plate diameters DB. Then, the average aspect ratio of the particles (DBave / DAave) is calculated from the average maximum plate thickness DAave and the average plate diameter DBave.

[0135] When the magnetic powder comprises a powder of hexagonal ferrite particles, the average particle volume of the magnetic powder is preferably 5900 nm 3 Less than or equal to 500 nm, preferably 3 More than 3400nm 3 Less than or equal to 1000 nm, and even more preferably less than 1000 nm 3 More than 2500nm 3 The average particle volume of the magnetic powder is 5900 nm or less. 3 If the average particle size of the magnetic powder is 30 nm or less, the same effect as when the average particle volume of the magnetic powder is 500 nm or less can be obtained. 3 If the average particle size of the magnetic powder is 12 nm or more, the same effect as in the case where the average particle size of the magnetic powder is 12 nm or more can be obtained.

[0136] The average particle volume of the magnetic powder is calculated as follows. First, the average maximum plate thickness DAave and the average plate diameter DBave are calculated using the above-mentioned method for calculating the average particle size of the magnetic powder. Next, the average volume V of the ε iron oxide particles is calculated using the following formula. V=3√3 / 8×DAave×DBave×DBave 2

[0137] According to a particularly preferred embodiment of the present technology, the magnetic powder may be barium ferrite magnetic powder or strontium ferrite magnetic powder, more preferably barium ferrite magnetic powder. The barium ferrite magnetic powder includes magnetic particles of iron oxide having barium ferrite as a main phase (hereinafter referred to as "barium ferrite particles"). The barium ferrite magnetic powder has high reliability in data recording, for example, the coercive force does not decrease even in a high temperature and high humidity environment. From this viewpoint, the barium ferrite magnetic powder is preferable as the magnetic powder.

[0138] The average particle size of the barium ferrite magnetic powder is 50 nm or less, more preferably 10 nm or more and 40 nm or less, and even more preferably 12 nm or more and 25 nm or less.

[0139] When the magnetic layer 13 contains barium ferrite magnetic powder as the magnetic powder, the average thickness tm [nm] of the magnetic layer 13 is preferably 35 nm≦tm≦100 nm, and particularly preferably 80 nm or less. In addition, the coercive force Hc measured in the thickness direction (perpendicular direction) of the magnetic recording medium 10 is preferably 160 kA / m or more and 280 kA / m or less, more preferably 165 kA / m or more and 275 kA / m or less, and even more preferably 170 kA / m or more and 270 kA / m or less.

[0140] (Variation 4) The magnetic powder may contain a powder of nanoparticles containing Co-containing spinel ferrite (hereinafter referred to as "cobalt ferrite particles") instead of the powder of ε iron oxide particles. The cobalt ferrite particles preferably have uniaxial anisotropy. The cobalt ferrite particles have, for example, a cubic or nearly cubic shape. The Co-containing spinel ferrite may further contain at least one of Ni, Mn, Al, Cu, and Zn in addition to Co.

[0141] The Co-containing spinel ferrite has, for example, an average composition represented by the following formula. Co x M y FeO Z (In formula (1), M is, for example, at least one metal selected from the group consisting of Ni, Mn, Al, Cu, and Zn. x is a value within the range of 0.4≦x≦1.0. y is a value within the range of 0≦y≦0.3. However, x and y satisfy the relationship of (x+y)≦1.0. z is a value within the range of 3≦z≦4. A part of Fe may be substituted with another metal element.)

[0142] When the magnetic powder contains cobalt ferrite particles, the average particle size of the magnetic powder is preferably 25 nm or less, more preferably 10 nm or more and 23 nm or less. When the average particle size of the magnetic powder is 25 nm or less, good electromagnetic conversion characteristics (e.g., SNR) can be obtained in a high recording density magnetic recording medium 10. On the other hand, when the average particle size of the magnetic powder is 10 nm or more, the dispersibility of the magnetic powder is further improved, and better electromagnetic conversion characteristics (e.g., SNR) can be obtained. When the magnetic powder contains cobalt ferrite particles, the average aspect ratio of the magnetic powder is the same as that of the above-mentioned embodiment. The average particle size and average aspect ratio of the magnetic powder are also calculated in the same manner as that of the above-mentioned embodiment.

[0143] The average particle volume of the magnetic powder is preferably 15,000 nm 3 Less than 1000 nm, more preferably 3 More than 12000nm 3The average particle volume of the magnetic powder is 15,000 nm or less. 3 When the average particle size of the magnetic powder is 25 nm or less, the same effect as when the average particle volume of the magnetic powder is 1000 nm or less can be obtained. 3 With this or more, the same effect as when the average particle size of the magnetic powder is 10 nm or more can be obtained. Note that the average particle volume of the magnetic powder is calculated in the same manner as in the above-mentioned embodiment (the method for calculating the average particle volume when the ε iron oxide particles are cubic or nearly cubic).

[0144] The coercive force Hc of the cobalt ferrite magnetic powder is preferably 2500 Oe or more, and more preferably 2600 Oe or more and 3500 Oe or less.

[0145] (Variation 5) The magnetic recording medium 10 may further include a barrier layer 15 provided on at least one surface of the substrate 11, as shown in FIG. 6. The barrier layer 15 is a layer for suppressing dimensional changes of the substrate 11 depending on the environment. For example, one example of a cause of the dimensional changes is the hygroscopicity of the substrate 11, and the barrier layer 15 can reduce the rate of moisture penetration into the substrate 11. The barrier layer 15 includes, for example, a metal or a metal oxide. The metal here may be, for example, at least one of Al, Cu, Co, Mg, Si, Ti, V, Cr, Mn, Fe, Ni, Zn, Ga, Ge, Y, Zr, Mo, Ru, Pd, Ag, Ba, Pt, Au, and Ta. The metal oxide may be, for example, a metal oxide including one or more of the above metals. More specifically, for example, at least one of Al2O3, CuO, CoO, SiO2, Cr2O3, TiO2, Ta2O5, and ZrO2 can be used. The barrier layer 15 may also contain diamond-like carbon (DLC) or diamond.

[0146] The average thickness of the barrier layer 15 is preferably 20 nm or more and 1000 nm or less, more preferably 50 nm or more and 1000 nm or less. The average thickness of the barrier layer 15 is determined in the same manner as the average thickness of the magnetic layer 13. However, the magnification of the TEM image is appropriately adjusted according to the thickness of the barrier layer 15.

[0147] (Variation 6) In the above embodiment, a case has been described in which a large number of protrusions 14A provided on the surface of the back layer 14 are transferred to the surface 13S of the magnetic layer 13 to form a large number of holes 13A in the surface 13S of the magnetic layer 13, but the method of forming a large number of holes 13A is not limited to this. For example, a large number of holes 13A may be formed in the surface 13S of the magnetic layer 13 by adjusting the type of solvent contained in the paint for forming the magnetic layer and the drying conditions of the paint for forming the magnetic layer.

[0148] (Variation 7) The magnetic recording medium 10 according to the embodiment described above may be used in a library device. In this case, the library device may include a plurality of recording / reproducing devices 30 according to the embodiment described above. EXAMPLES

[0149] The present disclosure will be specifically described below using examples, but the present disclosure is not limited to these examples.

[0150] In the following examples and comparative examples, the squareness ratio S1 in the vertical direction, the squareness ratio S2 in the longitudinal direction, the pore distribution (pore volume, pore diameter of maximum pore volume during desorption), BET specific surface area, average aspect ratio, average particle size of the magnetic powder, average particle volume of the magnetic powder, average thickness of the magnetic layer, average thickness of the underlayer, average thickness of the back layer, average thickness of the substrate, and the arithmetic mean roughness of the surface of the magnetic layer are values ​​determined by the measurement method described in the above-mentioned embodiment.

[0151] [Example 1] The magnetic recording medium of Example 1 was obtained as follows.

[0152] <Preparation process of paint for forming magnetic layer> The magnetic layer-forming paint was prepared as follows. First, the first composition having the following composition was kneaded with an extruder. Next, the kneaded first composition and the second composition having the following composition were added to a stirring tank equipped with a disperser and premixed. Then, further sand mill mixing was performed and filtering was performed to prepare the magnetic layer-forming paint.

[0153] (First composition) The components and their weights in the first composition are as follows: Barium ferrite (BaFe 12 O 19 ) Particle powder (hexagonal plate shape, average aspect ratio 2.8, average particle volume 1950 nm 3 ):100 parts by mass Vinyl chloride resin (cyclohexanone solution 30% by weight): 42 parts by weight (including solvent) (Degree of polymerization 300, Mn=10000, polar group OSO3K=0.07mmol / g, Contains secondary OH=0.3mmol / g. Aluminum oxide powder: 5 parts by weight (α-Al2O3, average particle size 0.1 μm) Carbon black (manufactured by Tokai Carbon Co., Ltd., product name: Seast TA): 2 parts by weight

[0154] (Second composition) The components and their weights in the second composition are as follows: Vinyl chloride resin: 3 parts by weight (including solution) (Resin solution: resin 30% by mass, cyclohexanone 70% by mass) n-Butyl stearate: 2 parts by weight Methyl ethyl ketone: 121.3 parts by weight Toluene: 121.3 parts by weight Cyclohexanone: 60.7 parts by weight

[0155] To the magnetic layer-forming coating material prepared as described above, 4 parts by mass of polyisocyanate (product name: Coronate L, manufactured by Tosoh Corporation) as a curing agent and 2 parts by mass of stearic acid as a fatty acid of the lubricant were added.

[0156] <Preparation process of paint for forming base layer> The paint for forming the undercoat layer was prepared as follows. First, the third composition having the following composition was kneaded with an extruder. Next, the kneaded third composition and the fourth composition having the following composition were added to a stirring tank equipped with a disperser and premixed. Then, further mixing was performed with a sand mill and filtering was performed to prepare the paint for forming the undercoat layer.

[0157] (Third composition) The components and their weights in the third composition are as follows: ·Acicular iron oxide powder (α-Fe2O3, average major axis length 0.15μm): 100 parts by mass Vinyl chloride resin: 60.6 parts by weight (including solution) (Resin solution: resin 30% by mass, cyclohexanone 70% by mass) Carbon black (average particle size 20 nm): 10 parts by weight

[0158] (4th composition) The components and their weights in the fourth composition are as follows. Polyurethane resin UR8200 (manufactured by Toyobo): 18.5 parts by weight n-Butyl stearate: 2 parts by weight Methyl ethyl ketone: 108.2 parts by weight Toluene: 108.2 parts by mass Cyclohexanone: 18.5 parts by weight

[0159] To the coating material for forming an undercoat layer prepared as described above, 4 parts by mass of polyisocyanate (product name: Coronate L, manufactured by Tosoh Corporation) as a curing agent and 2 parts by mass of stearic acid as a fatty acid of a lubricant were added.

[0160] <Preparation process of paint for forming back layer> The coating material for forming the back layer was prepared as follows: The following raw materials were mixed in a stirring tank equipped with a disperser, and the mixture was filtered to prepare the coating material for forming the back layer. Small particle size carbon black powder (average particle size (D50) 20 nm): 90 parts by weight Large particle size carbon black powder (average particle size (D50) 270 nm): 10 parts by weight Polyester polyurethane (manufactured by Tosoh Corporation, product name: N-2304): 100 parts by weight Methyl ethyl ketone: 500 parts by weight Toluene: 400 parts by weight Cyclohexanone: 100 parts by weight

[0161] <Coating process> Using the magnetic layer forming paint and the undercoat layer forming paint prepared as described above, a base layer with an average thickness of 0.6 μm and a magnetic layer with an average thickness of 80 nm were formed on one main surface of a long polyester film with an average thickness of 4.0 μm, which is a non-magnetic support, as follows. First, the undercoat layer forming paint was applied to one main surface of the polyester film and dried to form a base layer. Next, the magnetic layer was formed by applying the magnetic layer forming paint on the base layer and drying it. During drying of the magnetic layer forming paint, the magnetic powder was magnetically oriented in the thickness direction of the film by a solenoid coil. In addition, the drying conditions (drying temperature and drying time) of the magnetic layer forming paint were adjusted, and the squareness ratio S1 in the thickness direction (vertical direction) and the squareness ratio S2 in the longitudinal direction of the magnetic recording medium were set to the values ​​shown in Table 1 below. Next, the coating material for forming the back layer was applied onto the other main surface of the polyester film, dried, and calendered to form a back layer having an average thickness of 0.3 μm, thereby obtaining a magnetic recording medium.

[0162] <Calendar process and transfer process> Then, a calendaring process was performed to smooth the surface of the magnetic layer. Next, the magnetic recording medium with the smoothed surface of the magnetic layer was wound into a roll, and then the magnetic recording medium was heat-treated at 60°C for 10 hours in this state. Then, the magnetic recording medium was rewound into a roll so that the end located on the inner circumference side was reversely positioned on the outer circumference side, and then the magnetic recording medium was heat-treated again at 60°C for 10 hours in this state. As a result, many protrusions on the surface of the back layer were transferred to the surface of the magnetic layer, and many holes were formed on the surface of the magnetic layer.

[0163] <Cutting process> The magnetic recording medium obtained as described above was cut into a width of 1 / 2 inch (12.65 mm). This resulted in the desired long magnetic recording medium (average thickness 5.6 μm). The BET specific surface area of ​​the obtained magnetic recording medium after removing the lubricant and drying was 4 m2. 2 / g.

[0164] [Example 2] A magnetic recording medium as Example 2 was obtained in the same manner as in Example 1 above, except that the average thickness of the underlayer was 0.8 μm.

[0165] [Examples 3 to 5] In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) and the squareness ratio S2 in the longitudinal direction of the magnetic recording medium to the values ​​shown in Table 1, but otherwise the magnetic recording media were obtained in the same manner as in Example 1 above, as Examples 3 to 5.

[0166] [Example 6] The average thickness of the underlayer was 0.9 μm, the average thickness of the back layer was 0.4 μm, and the average thickness of the substrate was 4.2 μm. In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) of the magnetic recording medium and the squareness ratio S2 in the longitudinal direction to the values ​​shown in Table 1. In addition, the heating conditions in the transfer process were adjusted to set the BET specific surface area to 4.5 m 2 Except for these, a magnetic recording medium was obtained as Example 6 in the same manner as in Example 1 above.

[0167] [Example 7] The average thickness of the underlayer was 0.7 μm. In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) of the magnetic recording medium and the squareness ratio S2 in the longitudinal direction to the values ​​shown in Table 1. In the transfer process, the heating conditions were adjusted to set the BET specific surface area to 5.0 m. 2 Except for these, a magnetic recording medium was obtained as Example 7 in the same manner as in Example 1 above.

[0168] [Example 8] In the preparation process of the paint for forming the magnetic layer, strontium ferrite particles (hexagonal plate shape, average aspect ratio 3.0, average particle size 21.3 nm, particle volume 2000 nm) were used as the magnetic powder. 3 ) was used. In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) and the squareness ratio S2 in the longitudinal direction of the magnetic recording medium to the values ​​shown in Table 1. Except for these, the magnetic recording medium was obtained as in Example 1 above.

[0169] [Example 9] In the preparation process of the paint for forming the magnetic layer, a powder of ε iron oxide particles (spherical, average aspect ratio 1.1, average particle size 16 nm, particle volume 2150 nm) was used as the magnetic powder. 3 ) was used. In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) and the squareness ratio S2 in the longitudinal direction of the magnetic recording medium to the values ​​shown in Table 1. Except for these, the magnetic recording medium was obtained as in Example 9 in the same manner as in Example 1 above.

[0170] [Example 10] In the preparation process of the paint for forming the magnetic layer, cobalt ferrite powder (cubic, average aspect ratio 1.7, average particle size 18.5 nm, particle volume 2200 nm) was used as the magnetic powder. 3) was used. In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) and the squareness ratio S2 in the longitudinal direction of the magnetic recording medium to the values ​​shown in Table 1. Except for these, the magnetic recording medium was obtained as Example 10 in the same manner as in Example 1 above.

[0171] [Example 11] The average thickness of the undercoat layer was 0.9 μm, the average thickness of the back layer was 0.4 μm, and the average thickness of the substrate was 4.2 μm. The amount of small particle carbon black powder (average particle diameter (D50) 20 nm) in the paint for forming the back layer was 80 parts by mass, and the amount of large particle carbon black powder (average particle diameter (D50) 270 nm) was 20 parts by mass. The heating conditions in the transfer process were adjusted to reduce the pore volume to 0.023 cm 3 / g, and the pore diameter of the maximum pore volume during desorption was 9 nm. Furthermore, in the coating process, the drying conditions were adjusted, and the squareness ratio S1 in the thickness direction (vertical direction) and the squareness ratio S2 in the longitudinal direction of the magnetic recording medium were set to the values ​​shown in Table 1. Except for these, the magnetic recording medium was obtained as Example 11 in the same manner as in Example 1 above.

[0172] [Example 12] The average thickness of the underlayer was 0.9 μm, the average thickness of the back layer was 0.4 μm, and the average thickness of the substrate was 4.2 μm. In addition, the heating conditions in the transfer process were adjusted to set the pore diameter of the maximum pore volume during desorption to 10 nm. In addition, in the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) of the magnetic recording medium and the squareness ratio S2 in the longitudinal direction to the values ​​shown in Table 1. Except for these, the magnetic recording medium was obtained as Example 12 in the same manner as in Example 1 above.

[0173] [Example 13] The average thickness of the back layer was 0.5 μm, and the average thickness of the substrate was 3.6 μm. In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) of the magnetic recording medium and the squareness ratio S2 in the longitudinal direction to the values ​​shown in Table 1. Except for these, the magnetic recording medium was obtained as Example 13 in the same manner as in Example 1 above.

[0174] [Example 14] In forming the coating material for forming the back layer, 70 parts by mass of small particle size carbon black powder (average particle size (D50) 50 nm) was blended in place of the small particle size carbon black powder (average particle size (D50) 20 nm), and the blending amount of large particle size carbon black powder (average particle size (D50) 270 nm) was changed to 30 parts by mass. In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) and the squareness ratio S2 in the longitudinal direction of the magnetic recording medium to the values ​​shown in Table 1. Furthermore, the heating conditions in the transfer process were adjusted to set the BET specific surface area to 6.0 m 2 Except for these, a magnetic recording medium was obtained as Example 16 in the same manner as in Example 1. The pore diameter at the maximum pore volume during desorption was 12 nm.

[0175] [Example 15] In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) and the squareness ratio S2 in the longitudinal direction of the magnetic recording medium to the values ​​shown in Table 1. Except for these, the magnetic recording medium was obtained as Example 17 in the same manner as in Example 1 above.

[0176] [Example 16] The average thickness of the underlayer was 0.9 μm, the average thickness of the back layer was 0.4 μm, and the average thickness of the substrate was 4.2 μm. In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) of the magnetic recording medium and the squareness ratio S2 in the longitudinal direction to the values ​​shown in Table 1. Except for these, the magnetic recording medium was obtained as Example 18 in the same manner as in Example 1 above. The BET specific surface area was 3.9 m 2 / g.

[0177] [Example 17] In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) and the squareness ratio S2 in the longitudinal direction of the magnetic recording medium to the values ​​shown in Table 1. Except for these, the magnetic recording medium was obtained as Example 19 in the same manner as in Example 1 above. The BET specific surface area was 3.8 m 2 / g.

[0178] [Example 18] In the preparation process of the coating material for forming the magnetic layer, the magnetic powder had an average aspect ratio of 2.5, an average particle size of 19.0 nm, and an average particle volume of 1600 nm. 3 A magnetic recording medium was obtained as Example 20 in the same manner as in Example 1, except that a powder of hexagonal plate-shaped barium ferrite particles was used. The pore diameter of the maximum pore volume during desorption was 7 nm.

[0179] [Example 19] In the preparation process of the coating material for forming the magnetic layer, the magnetic powder had an average aspect ratio of 2.3, an average particle size of 17.0 nm, and an average particle volume of 1300 nm. 3 A magnetic recording medium was obtained as Example 21 in the same manner as in Example 1, except that a powder of hexagonal plate-shaped barium ferrite particles was used. The pore diameter of the maximum pore volume during desorption was 6 nm.

[0180] [Example 20] The average thickness of the magnetic layer was 60 nm. In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (perpendicular direction) of the magnetic recording medium and the squareness ratio S2 in the longitudinal direction to the values ​​shown in Table 1. Except for these, the magnetic recording medium was obtained as Example 22 in the same manner as in Example 1 above. The BET specific surface area was 3.9 m 2 / g.

[0181] [Example 21] The average thickness of the magnetic layer was 40 nm. In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (perpendicular direction) of the magnetic recording medium and the squareness ratio S2 in the longitudinal direction to the values ​​shown in Table 1. Except for these, the magnetic recording medium was obtained as Example 23 in the same manner as in Example 1 above. The BET specific surface area was 3.8 m 2 / g.

[0182] [Example 22] In the preparation process of the coating material for forming the magnetic layer, the magnetic powder has an average particle size of 23.0 nm and an average particle volume of 2500 nm 3 The powder of hexagonal plate-shaped barium ferrite particles having the above formula was used. The average thickness of the underlayer was set to 0.5 μm. Except for the above, the magnetic recording medium was obtained as Example 24 in the same manner as in Example 1.

[0183] [Example 23] In the preparation process of the coating material for forming the magnetic layer, the magnetic powder has an average particle size of 23.0 nm and an average particle volume of 2500 nm 3 A magnetic recording medium was obtained as Example 25 in the same manner as in Example 1, except that a powder of hexagonal plate-shaped barium ferrite particles was used.

[0184] [Example 24] In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) of the magnetic recording medium and the squareness ratio S2 in the longitudinal direction to the values ​​shown in Table 1. Furthermore, the heating conditions in the transfer process were adjusted to set the BET specific surface area to 3.5 m 2 Except for these, the magnetic recording medium was obtained as Example 26 in the same manner as in Example 1 above.

[0185] [Comparative Example 1] In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) of the magnetic recording medium and the squareness ratio S2 in the longitudinal direction to the values ​​shown in Table 3. Furthermore, the heating conditions in the transfer process were adjusted to set the BET specific surface area to 3.0 m 2Except for these, a magnetic recording medium was obtained as Comparative Example 1 in the same manner as in Example 1.

[0186] [Comparative Example 2] In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) and the squareness ratio S2 in the longitudinal direction of the magnetic recording medium to the values ​​shown in Table 3. The average thickness of the underlayer was set to 1.2 μm. Apart from these, a magnetic recording medium was obtained as Comparative Example 2 in the same manner as in Example 1 above.

[0187] [Comparative Example 3] In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (perpendicular direction) of the magnetic recording medium and the squareness ratio S2 in the longitudinal direction to the values ​​shown in Table 3. The average thickness of the underlayer was set to 1.2 μm. Furthermore, the heating conditions in the transfer process were adjusted to set the BET specific surface area to 2.0 m. 2 Except for these, a magnetic recording medium was obtained as Comparative Example 3 in the same manner as in Example 1 above.

[0188] [Comparative Example 4] In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) of the magnetic recording medium and the squareness ratio S2 in the longitudinal direction to the values ​​shown in Table 3. Furthermore, the heating conditions in the transfer process were adjusted to set the BET specific surface area to 2.0 m 2 Except for these, a magnetic recording medium was obtained as Comparative Example 4 in the same manner as in Example 1 above.

[0189] [Comparative Example 5] In forming the coating material for forming the back layer, 80 parts by mass of small particle size carbon black powder (average particle size (D50) 50 nm) was blended in place of the small particle size carbon black powder (average particle size (D50) 20 nm), and the blending amount of large particle size carbon black powder (average particle size (D50) 270 nm) was changed to 20 parts by mass. In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) and the squareness ratio S2 in the longitudinal direction of the magnetic recording medium to the values ​​shown in Table 3. Furthermore, the heating conditions in the transfer process were adjusted to set the pore volume to 0.018 cm 3 / g, and the BET specific surface area is 3.0 m 2 Except for these, a magnetic recording medium was obtained as Comparative Example 5 in the same manner as in Example 1 above.

[0190] [Comparative Example 6] In forming the coating material for forming the back layer, 90 parts by mass of small particle size carbon black powder (average particle size (D50) 50 nm) was blended in place of the small particle size carbon black powder (average particle size (D50) 20 nm). In addition, in the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) of the magnetic recording medium and the squareness ratio S2 in the longitudinal direction to the values ​​shown in Table 3. Furthermore, in the transfer process, the heating conditions were adjusted to set the pore volume to 0.015 cm 3 / g, and the BET specific surface area is 2.5 m 2 Except for these, a magnetic recording medium was obtained as Comparative Example 6 in the same manner as in Example 1 above.

[0191] [Comparative Example 7] In forming the coating material for forming the back layer, 100 parts by mass of small particle diameter carbon black powder (average particle diameter (D50) 20 nm) was blended, and the blending amount of large particle diameter carbon black powder (average particle diameter (D50) 270 nm) was set to 0 parts by mass. In the coating process, the drying conditions were adjusted, and the squareness ratio S1 in the thickness direction (vertical direction) and the squareness ratio S2 in the longitudinal direction of the magnetic recording medium were set to the values ​​shown in Table 3. Furthermore, the heating conditions in the transfer process were adjusted, and the pore volume was set to 0.015 cm 3 / g, the pore diameter of the maximum pore volume during desorption is 5 nm, and the BET specific surface area is 2.0 m 2 Except for these, a magnetic recording medium was obtained as Comparative Example 7 in the same manner as in Example 1 above.

[0192] [Comparative Example 8] In forming the coating material for forming the back layer, 100 parts by mass of small particle size carbon black powder (average particle size (D50) 20 nm) was blended, and the blending amount of large particle size carbon black powder (average particle size (D50) 270 nm) was set to 0 parts by mass. The average thickness of the undercoat layer was set to 0.5 μm. In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) of the magnetic recording medium and the squareness ratio S2 in the longitudinal direction to the values ​​shown in Table 3. Furthermore, the heating conditions in the transfer process were adjusted to set the pore volume to 0.015 cm 3 / g, the pore diameter of the maximum pore volume during desorption is 5 nm, and the BET specific surface area is 2.0 m 2 Except for these, a magnetic recording medium was obtained as Comparative Example 7 in the same manner as in Example 1 above.

[0193] [Comparative Example 9] The average thickness of the underlayer was 1.0 μm, and the average thickness of the back layer was 0.5 μm. In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) of the magnetic recording medium and the squareness ratio S2 in the longitudinal direction to the values ​​shown in Table 3. In addition, the heating conditions in the transfer process were adjusted to set the BET specific surface area to 3.8 m. 2 Except for these, a magnetic recording medium was obtained as Comparative Example 9 in the same manner as in Example 1 above.

[0194] [Comparative Example 10] The average thickness of the underlayer was 1.4 μm. In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (perpendicular direction) of the magnetic recording medium and the squareness ratio S2 in the longitudinal direction to the values ​​shown in Table 3. In the transfer process, the heating conditions were adjusted to set the BET specific surface area to 3.5 m. 2Except for these, a magnetic recording medium was obtained as Comparative Example 10 in the same manner as in Example 1 above.

[0195] [Comparative Examples 11 and 12] In the coating process, the drying conditions were adjusted to set the squareness ratio S1 in the thickness direction (vertical direction) and the squareness ratio S2 in the longitudinal direction of the magnetic recording medium to the values ​​shown in Table 1. Except for these, magnetic recording media were obtained as Comparative Examples 11 and 12 in the same manner as in Example 1 above.

[0196] [evaluation] The above-mentioned friction coefficient ratios (μ B / μ A ) and friction coefficient ratio (μ C(1000) / μ C(5) In addition to the above, the following evaluations were performed:

[0197] (SNR) The SNR (electromagnetic conversion characteristics) of the magnetic recording medium was measured in a 25°C environment using a 1 / 2 inch tape transport device (MTS Transport, manufactured by Mountain Engineering II) equipped with a recording / reproducing head and a recording / reproducing amplifier. A ring head with a gap length of 0.2 μm was used as the recording head, and a GMR head with a shield distance of 0.1 μm was used as the reproducing head. The relative speed was 6 m / s, the recording clock frequency was 160 MHz, and the recording track width was 2.0 μm. The SNR was calculated based on the method described in the following document. The results are shown in Tables 1 and 3 as relative values ​​with the SNR of Example 1 taken as 1 dB. Y. Okazaki: “An Error Rate Emulation System.”, IEEE Trans. Man., 31, pp.3093-3095(1995)

[0198] Table 2 shows the configurations and evaluation results of the magnetic recording media in each of the examples and comparative examples. [Table 2]

[0199] As shown in Table 2, in Examples 1 to 24, the overall BET specific surface area of ​​the magnetic recording medium in a dry state after removing the lubricant was 3.5 m 2 / g or more, the lubricant was stably supplied to the interface between the magnetic recording medium and the magnetic head even after repeated recording or reproduction, and an increase in the friction coefficient ratio was suppressed. On the other hand, in Comparative Examples 1, 3 to 8, the BET specific surface area of ​​the entire magnetic recording medium in a dry state after removing the lubricant was 3.5 m 2 / g, an increase in the friction coefficient ratio was observed after repeated recording or reproduction.

[0200] In Comparative Examples 2, 9, and 10, the overall BET specific surface area of ​​the magnetic recording medium after removing the lubricant and drying was 3.5 m 2 / g or more, since the average thickness of the underlayer exceeds 0.9 μm, the Young's modulus is high and an increase in the friction coefficient ratio after repeated recording or reproduction was also observed.

[0201] In addition, in Examples 1 to 24, the squareness ratio S1 in the perpendicular direction (thickness direction) of the magnetic recording medium was 65% or more, and therefore a good SNR was obtained. In contrast, in Comparative Examples 11 and 12, the squareness ratio S1 in the perpendicular direction (thickness direction) of the magnetic recording medium was less than 65%, and therefore degradation of the SNR was observed.

[0202] While the present disclosure has been specifically described above by giving embodiments and modifications thereof, the present disclosure is not limited to the above-described embodiments, and various modifications are possible.

[0203] For example, the configurations, methods, steps, shapes, materials, and values ​​given in the above-mentioned embodiments and their modified examples are merely examples, and different configurations, methods, steps, shapes, materials, and values ​​may be used as necessary. Specifically, the magnetic recording medium of the present disclosure may include components other than the substrate, underlayer, magnetic layer, back layer, and barrier layer. In addition, the chemical formulas of compounds, etc. are representative, and are not limited to the valences, etc. given as long as they are general names of the same compounds.

[0204] Furthermore, the configurations, methods, steps, shapes, materials, numerical values, and the like of the above-described embodiments and their modified examples can be combined with each other without departing from the spirit of this disclosure.

[0205] In addition, in the numerical ranges described in stages in this specification, the upper limit or lower limit of a certain numerical range may be replaced with the upper limit or lower limit of another numerical range. Unless otherwise specified, the materials exemplified in this specification may be used alone or in combination of two or more.

[0206] As described above, according to the magnetic recording medium as one embodiment of the present disclosure, good running performance can be achieved during use. Note that the effects of the present disclosure are not limited to the above, and may be any of the effects described in this specification. In addition, the present technology may have the following configurations. (1) A tape-shaped magnetic recording medium, A substrate; An undercoat layer provided on the substrate; a magnetic layer provided on the underlayer; having The substrate contains polyester as a main component, The average thickness of the underlayer is 0.9 μm or less, the underlayer and the magnetic layer contain a lubricant, the magnetic layer has a surface having a large number of holes, and the arithmetic mean roughness Ra of the surface is 2.5 nm or less; The overall BET specific surface area of ​​the magnetic recording medium after the lubricant has been removed and the magnetic recording medium is in a dry state is 3.5 m 2 / g or more, The squareness ratio of the magnetic recording medium in the perpendicular direction is 65% or more; The average thickness of the magnetic layer is 90 nm or less, The average thickness of the magnetic recording medium is 5.6 μm or less. Magnetic recording media. (2) The Young's modulus of the magnetic recording medium is 7.78 GPa or less. The magnetic recording medium according to (1) above. (3) The average thickness of the substrate is 4.2 μm or less. The magnetic recording medium according to (1) or (2) above. (4) The substrate further includes a back layer provided on the opposite side of the base layer, The average thickness of the back layer is 0.3 μm or more and 0.5 μm or less. The magnetic recording medium according to any one of (1) to (3) above. (5) The average thickness of the undercoat layer is 0.5 μm or more. The magnetic recording medium according to any one of (1) to (4) above. (6) The overall average pore diameter of the magnetic recording medium as determined by the BJH method is 6 nm or more and 12 nm or less. The magnetic recording medium according to any one of (1) to (5) above. (7) The ratio μB / μA of the dynamic friction coefficient μA between the surface and the magnetic head when the tension applied to the magnetic recording medium is 0.4 N to the dynamic friction coefficient μB between the surface and the magnetic head when the tension applied to the magnetic recording medium is 1.2 N is 1.0 or more and 1.8 or less. The magnetic recording medium according to any one of (1) to (6) above. (8) The ratio μC(1000) / μC(5) of the dynamic friction coefficient μC(5) between the surface and the magnetic head at the 5th time from the start of running of the magnetic recording medium when a tension of 0.6 N is applied to the magnetic recording medium to the dynamic friction coefficient μC(1000) between the surface and the magnetic head at the 1000th time from the start of running of the magnetic recording medium when a tension of 0.6 N is applied to the magnetic recording medium is 1.2 or more and 1.8 or less. The magnetic recording medium according to any one of (1) to (7) above. (9) The magnetic layer includes a magnetic powder. The average aspect ratio of the magnetic powder is 1.1 or more and 3.0 or less. The magnetic recording medium according to any one of (1) to (8) above. (10) The magnetic layer includes a magnetic powder. The magnetic powder includes hexagonal ferrite containing at least one of Ba (barium) and Sr (strontium), ε iron oxide, or Co (cobalt)-containing spinel ferrite. The magnetic recording medium according to any one of (1) to (9) above. (11) The magnetic layer includes a magnetic powder. The average particle size of the magnetic powder is 25 nm or less. The magnetic recording medium according to any one of (1) to (10) above. (12) The lubricant has the following general formula: <1> From the general formula <4> The compound includes at least one of the compounds represented by The magnetic recording medium according to any one of (1) to (11) above. CH3(CH2) n COOH… <1> (However, the above general formula <1> In the formula, n is an integer selected from the range of 14 to 22. CH3(CH2) p COO(CH2) q CH3… <2> (However, the above general formula <2> In the formula, p is an integer selected from the range of 14 to 22, and q is an integer selected from the range of 2 to 5. CH3(CH2) n CH=CH(CH2) m COOH… <3> (However, the above general formula <3> In the formula, n+m is an integer selected from the range of 12 to 20. CH3(CH2) p COO-(CH2) q CH(CH3)2… <4> (However, the above general formula <4> In the formula, p is an integer selected from the range of 14 to 22, and q is an integer selected from the range of 1 to 3. (13) the underlayer has a large number of holes, The holes in the magnetic layer and the holes in the underlayer are connected to each other. The magnetic recording medium according to any one of (1) to (12) above. (14) The arithmetic mean roughness Ra of the surface of the magnetic layer is 0.8 nm or more. The magnetic recording medium according to any one of (1) to (13) above. (15) The overall BET specific surface area of ​​the magnetic recording medium after the lubricant has been removed and the magnetic recording medium is in a dry state is 4.0 m 2 / g or more The magnetic recording medium according to any one of (1) to (14) above. (16) The overall BET specific surface area of ​​the magnetic recording medium after the lubricant has been removed and the magnetic recording medium is in a dry state is 4.5 m 2 / g or more The magnetic recording medium according to any one of (1) to (15) above. (17) The overall BET specific surface area of ​​the magnetic recording medium after the lubricant has been removed and the magnetic recording medium is in a dry state is 5.0 m 2 / g or more The magnetic recording medium according to any one of (1) to (16) above. (18) The overall BET specific surface area of ​​the magnetic recording medium after the lubricant has been removed and the magnetic recording medium is in a dry state is 7.0 m 2 / g or less The magnetic recording medium according to any one of (1) to (17) above. (19) The overall BET specific surface area of ​​the magnetic recording medium after the lubricant has been removed and the magnetic recording medium is in a dry state is 6.0 m 2 / g or less The magnetic recording medium according to any one of (1) to (18) above. (20) The overall BET specific surface area of ​​the magnetic recording medium after the lubricant has been removed and the magnetic recording medium is in a dry state is 5.5 m 2 / g or less The magnetic recording medium according to any one of (1) to (19) above. (twenty one) a feeding section capable of sequentially feeding out tape-shaped magnetic recording media; a winding section capable of winding up the magnetic recording medium fed from the feeding section; a magnetic head capable of writing information to the magnetic recording medium and reading information from the magnetic recording medium while contacting the magnetic recording medium traveling from the delivery section to the take-up section; Equipped with The magnetic recording medium is A substrate; An undercoat layer provided on the substrate; a magnetic layer provided on the underlayer; having The substrate contains polyester as a main component, The average thickness of the underlayer is 0.9 μm or less, the underlayer and the magnetic layer contain a lubricant, the magnetic layer has a surface having a large number of holes, and the arithmetic mean roughness Ra of the surface is 2.5 nm or less; The overall BET specific surface area of ​​the magnetic recording medium after the lubricant has been removed and the magnetic recording medium is in a dry state is 3.5 m 2 / g or more, The squareness ratio of the magnetic recording medium in the perpendicular direction is 65% or more; The average thickness of the magnetic layer is 90 nm or less, The average thickness of the magnetic recording medium is 5.6 μm or less. Magnetic recording and playback device. (twenty two) The tension applied to the magnetic recording medium in the longitudinal direction can be adjusted. The magnetic recording and reproducing device according to (21) above. (twenty three) A tape-shaped magnetic recording medium according to any one of (1) to (22) above, a housing for accommodating the magnetic recording medium; A magnetic recording medium cartridge comprising: [Explanation of symbols]

[0207] 10...magnetic recording medium, 11...substrate, 11A, 11B...main surfaces, 12...underlayer, 13...magnetic layer, 14...back layer, 20, 20A...ε iron oxide particles, 21...core portion, 22...shell portion, 22a...first shell portion, 22b...second shell portion, 30...recording and reproducing device, 31...spindle, 32...reel, 33, 34...driving device, 35...guide roller, 36...head unit, 37...communication interface, 38...control device, 41...server, 42...personal computer, 43...network.

Claims

1. A tape-shaped magnetic recording medium, A substrate; An undercoat layer provided on the substrate; a magnetic layer provided on the underlayer; having The substrate contains polyester as a main component, The Young's modulus of the magnetic recording medium is 7.78 GPa or less, the magnetic recording medium includes a lubricant; the magnetic layer has a surface having a large number of holes, and the arithmetic mean roughness Ra of the surface is 2.5 nm or less; The overall BET specific surface area of ​​the magnetic recording medium after the lubricant has been removed and the magnetic recording medium is in a dry state is 3.5 m 2 / g or more, The squareness ratio of the magnetic recording medium in the longitudinal direction is 35% or less, The average thickness of the magnetic layer is 90 nm or less, The average thickness of the magnetic recording medium is 5.6 μm or less, The magnetic layer contains magnetic powder, and the magnetic powder has an average particle volume of 1950 nm 3 is less than or equal to Magnetic recording media.

2. The average thickness of the magnetic recording medium is 5.2 μm or less.

2. The magnetic recording medium according to claim 1.

3. The data track width of the magnetic layer is 1500 nm or less.

3. The magnetic recording medium according to claim 1 or 2.

4. The average thickness of the magnetic layer is 70 nm or less. The magnetic recording medium according to any one of claims 1 to 3.

5. The average thickness of the substrate is 4.2 μm or less. The magnetic recording medium according to any one of claims 1 to 4.

6. The substrate further includes a back layer provided on the opposite side of the base layer, The average thickness of the back layer is 0.3 μm or more and 0.5 μm or less. The magnetic recording medium according to any one of claims 1 to 5.

7. The average thickness of the undercoat layer is 0.5 μm or more. The magnetic recording medium according to any one of claims 1 to 6.

8. The average pore diameter of the entire magnetic recording medium as determined by the BJH method is 6 nm or more and 12 nm or less. The magnetic recording medium according to any one of claims 1 to 7.

9. The ratio μB / μA of the dynamic friction coefficient μA between the surface and the magnetic head when the tension applied to the magnetic recording medium is 0.4 N to the dynamic friction coefficient μB between the surface and the magnetic head when the tension applied to the magnetic recording medium is 1.2 N is 1.0 or more and 1.8 or less. The magnetic recording medium according to any one of claims 1 to 8.

10. The ratio of the dynamic friction coefficient μC(1000) / μC(5) between the surface and the magnetic head at the fifth time from the start of running of the magnetic recording medium when a tension of 0.6 N is applied to the magnetic recording medium and the dynamic friction coefficient μC(1000) between the surface and the magnetic head at the 1000th time from the start of running of the magnetic recording medium when a tension of 0.6 N is applied to the magnetic recording medium is 1.2 or more and 1.8 or less. The magnetic recording medium according to any one of claims 1 to 9.

11. The average aspect ratio of the magnetic powder is 1.1 or more and 3.0 or less. The magnetic recording medium according to any one of claims 1 to 10.

12. The magnetic powder includes hexagonal ferrite containing at least one of Ba (barium) and Sr (strontium), ε iron oxide, or Co (cobalt)-containing spinel ferrite. The magnetic recording medium according to any one of claims 1 to 11.

13. The average particle size of the magnetic powder is 25 nm or less. The magnetic recording medium according to any one of claims 1 to 12.

14. The lubricant contains at least one of the compounds represented by the following general formulas <1> to <4>: The magnetic recording medium according to any one of claims 1 to 13. CH 3 (CH 2 ) n COOH …<1> (In the above general formula <1>, n is an integer selected from the range of 14 to 22.) CH 3 (CH 2 ) p COO(CH 2 ) q CH 3 …<2> (In the above general formula <2>, p is an integer selected from the range of 14 or more and 22 or less, and q is an integer selected from the range of 2 or more and 5 or less.) CH 3 (CH 2 ) n CH=CH(CH 2 ) m COOH …<3> (In the above general formula <3>, n+m is an integer selected from the range of 12 or more and 20 or less.) CH 3 (CH 2 ) p COO-(CH 2 ) q CH(CH 3 ) 2 …<4> (In the general formula <4>, p is an integer selected from the range of 14 or more and 22 or less, and q is an integer selected from the range of 1 or more and 3 or less.)

15. the underlayer has a large number of holes, The holes in the magnetic layer and the holes in the underlayer are connected to each other. The magnetic recording medium according to any one of claims 1 to 14.

16. The arithmetic mean roughness Ra of the surface of the magnetic layer is 0.8 nm or more. The magnetic recording medium according to any one of claims 1 to 15.

17. The overall BET specific surface area of ​​the magnetic recording medium after the lubricant has been removed and the magnetic recording medium is in a dry state is 4.0 m 2 / g or more The magnetic recording medium according to any one of claims 1 to 16.

18. The overall BET specific surface area of ​​the magnetic recording medium after the lubricant has been removed and the magnetic recording medium is in a dry state is 4.5 m 2 / g or more The magnetic recording medium according to any one of claims 1 to 17.

19. The overall BET specific surface area of ​​the magnetic recording medium after the lubricant has been removed and the magnetic recording medium is in a dry state is 5.0 m 2 / g or more The magnetic recording medium according to any one of claims 1 to 18.

20. The overall BET specific surface area of ​​the magnetic recording medium after the lubricant has been removed and the magnetic recording medium is in a dry state is 7.0 m 2 / g or less The magnetic recording medium according to any one of claims 1 to 19.

21. The overall BET specific surface area of ​​the magnetic recording medium after the lubricant has been removed and the magnetic recording medium is in a dry state is 6.0 m 2 / g or less The magnetic recording medium according to any one of claims 1 to 20.

22. The overall BET specific surface area of ​​the magnetic recording medium after the lubricant has been removed and the magnetic recording medium is in a dry state is 5.5 m 2 / g or less The magnetic recording medium according to any one of claims 1 to 21.

23. The average particle volume of the magnetic powder is 1600 nm 3 Is less than or equal to The magnetic recording medium according to any one of claims 1 to 22.

24. The average particle volume of the magnetic powder is 1300 nm 3 Is less than or equal to The magnetic recording medium according to any one of claims 1 to 22.

25. a feeding section capable of sequentially feeding out tape-shaped magnetic recording media; a winding section capable of winding up the magnetic recording medium fed from the feeding section; a magnetic head capable of writing information to the magnetic recording medium and reading information from the magnetic recording medium while contacting the magnetic recording medium traveling from the delivery section to the take-up section; Equipped with The magnetic recording medium is A substrate; An undercoat layer provided on the substrate; a magnetic layer provided on the underlayer; having The substrate contains polyester as a main component, The Young's modulus of the magnetic recording medium is 7.78 GPa or less, the magnetic recording medium includes a lubricant; the magnetic layer has a surface having a large number of holes, and the arithmetic mean roughness Ra of the surface is 2.5 nm or less; The overall BET specific surface area of ​​the magnetic recording medium after the lubricant has been removed and the magnetic recording medium is in a dry state is 3.5 m 2 / g or more, The squareness ratio of the magnetic recording medium in the longitudinal direction is 35% or less, The average thickness of the magnetic layer is 90 nm or less, The average thickness of the magnetic recording medium is 5.6 μm or less, The magnetic layer contains magnetic powder, and the magnetic powder has an average particle volume of 1950 nm 3 is less than or equal to Magnetic recording and playback device.

26. The tension applied to the magnetic recording medium in the longitudinal direction can be adjusted.

26. The magnetic recording and reproducing apparatus according to claim 25.

27. A tape-shaped magnetic recording medium; a housing for accommodating the magnetic recording medium; Equipped with The magnetic recording medium is A substrate; An undercoat layer provided on the substrate; a magnetic layer provided on the underlayer; having The substrate contains polyester as a main component, The Young's modulus of the magnetic recording medium is 7.78 GPa or less, the magnetic recording medium includes a lubricant; the magnetic layer has a surface having a large number of holes, and the arithmetic mean roughness Ra of the surface is 2.5 nm or less; The overall BET specific surface area of ​​the magnetic recording medium after the lubricant has been removed and the magnetic recording medium is in a dry state is 3.5 m 2 / g or more, The squareness ratio of the magnetic recording medium in the longitudinal direction is 35% or less, The average thickness of the magnetic layer is 90 nm or less, The average thickness of the magnetic recording medium is 5.6 μm or less, The magnetic layer contains magnetic powder, and the magnetic powder has an average particle volume of 1950 nm 3 Is less than or equal to Magnetic recording medium cartridge.

Citation Information

Patent Citations

  • Magnetic recording medium

    JP2002367151A

  • Magnetic recording medium

    JP2004334947A

  • Magnetic recording medium

    JP2006065953A

  • Magnetic recording medium

    JP2018106795A

  • Magnetic recording medium

    WO2019093447A1